Towards improved predictions of thermal inertia via the combined use of matric potential and machine learning - Xiangwei Wang; Anne Verhoef; Jiagui Hou; Lang Jia; Henrique Da Ros Carvalho; Hailong He (Soil and Tillage Research, 2026)

Moderate introgression in a single individual genome is sufficient to mislead phylogenomic inference of Triplophysa - Zitu Ma; He Gao; Chuanshuai Xie; Da Ji; Yongrui Lu; Haoyu Wang; Yili Cui; Francisco de Menezes Cavalcante Sassi; Dengyue Yuan; Haiping Liu; Luohao Xu (Molecular Phylogenetics and Evolution, 2026)

Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

NIR-responsive mesoporous core-shell nanoplatform with oxygen self-supply and cascade targeting for reversing doxorubicin resistance via synergistic chemo-phototherapy - Yufeng Li; Yuping Jiang; Kexuan Wang; Xinyi Liu; Rui Yang; Lu Han; Tao He; Na Li; Da Huo (Chemical Engineering Journal, 2026)

Bidirectional wave-induced mooring line failure in expanded ports: Mechanism analysis and mooring arrangement optimization - Da-chuan He; Ya-kun Liu; Xi Zhang; Ke Wang (Ocean Engineering, 2026)

Gecko tail regeneration-inspired composite hydrogel scaffolds with “socket-plug” architecture for dynamically programmed repair of infected bone defects - Minglang Zou; Yi Tang; Yongming Wang; Ling Mo; Menghuan Wang; Qing He; Zhenjin Xu; Liu Su; Pengfei Wang; Fang Luo; Da Huang; Jiewei Luo; et al. (Chemical Engineering Journal, 2026)

Photothermal Agents in Cancer Therapy: Applications and Development Prospects - Shiyu He; Shuaipeng Feng; Yiming Han; Qingqing Xu; Jiaru Lan; Donghua Di; Da Wang; Siling Wang; Huan Zhai; Qinfu Zhao (Chemical Engineering Journal, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

The luxury effect under environmental filtering: Drivers of residential plant diversity in 15 high-altitude cities - Yao Yao; Zhiwen Gao; Lin He; Luyi Lan; Xiaoya Yu; Ruishen Yang; Junwei Wang; Yuandong Hu; Qiong La; Liangjun Da (Journal of Environmental Management, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

Study on the relationship between surface deformation and internal fracturing of tunnel surrounding rock under uniaxial loading with multiple blasting disturbances - Tian-Xiao Chen; Shi-Da Xu; Ben-Guo He; Yuan-Hui Li; Jian-Yu Peng (Tunnelling and Underground Space Technology, 2026)

Optimizing multidimensional land use for flood regulation supply-demand matching: Evidence from a GWRF-SHAP model - Weihao Shi; Jian Tian; Jiahao Zhang; Aihemaiti Namaiti; Weijie He; Da Zhang; Jian Zeng (Journal of Environmental Management, 2026)

Apparent resistivity evaluation method of slurry diffusion-solidification and grouting effect of water-bearing fractured rock mass - Hao Xu; Zhen-zhong Xing; Sheng-quan He; Lian-zhi Yang; Yi Zhu; Da-zhao Song; Yu Zhang; Jin-tao Dang; Qiang Liu; Li-ming Qiu; Ping Wang (Journal of Applied Geophysics, 2026)

Mechanistic insights into hexamethylphosphoramide degradation and phosphorus recovery via mZVI/O3: Beyond conventional oxidation through iron-phosphorus speciation - Da Wang; Wenqian Hu; Yumeng Zheng; Zihan Xia; Haijun Cheng; Xiaohui Lu; Zhiqiao He; Stefanos Giannakis; Shuang Song; Jun Ma (Chemical Engineering Journal, 2026)

Integrating physiology, behavior, and transcriptomics to refine pesticide risk assessment: the case of flupyradifurone and Coccinella septempunctata - Yuxin Dong; Yajie Zhang; Boyang An; Wenqiu Yuan; Guy Smagghe; Qiuju Qin; Yunzhuan He; Da Wang (Journal of Pest Science, 2026)

Dynamics and drivers of last-resort antibiotic resistance genes during pilot-scale aerobic fermentation of municipal sludge and subsequent bok choy pot trials - Li-Tao Zhou; Da-Hai He; Jiang Li; Ruo-Xue He; Shi-Jin Ma; Guang-Yu Gong; Xiao-Shuang Zou; Sen Li; You-Fei Zhou; Wei-Jie Hu (Journal of Hazardous Materials, 2026)

Lithium isotope fractionation in LCT pegmatite systems: a density functional theory study - He-Feng Lin; Wen-Bin Zhu; Hai-Zhen Wei; Xi-Sheng Xu; Zhi-Qin Xu; M.R. Palmer; Shuang Chen; Jing Ma; Yin-Chuan Li; Da-Sheng Zuo; Ke Yang (Geochimica et Cosmochimica Acta, 2026)

Energy-efficiency optimization of tunnel lighting systems: an adaptive penalty function model considering combined parameters of inner wall reflectivity and luminaire layout - Hao Liu; Shiyong He; Weidong Tang; Da Xu; Jia’an Niu; Xin Tang; Zhonglang Yang; Bo Liang (Tunnelling and Underground Space Technology, 2026)

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

Pathways and geographical patterns of international shipping CO2 emissions in the future - Wen Yi; Huan Liu; Tingkun He; Weiwei Zhang; Xiaotong Wang; Songxin Zheng; Xiaodan Huang; Zhenyu Luo; Da Zhang; Kebin He (Science Bulletin, 2026)

Laboratory selection reveals flubendiamide resistance, fitness costs, and detoxification-related mechanisms in Spodoptera frugiperda: Insights for insecticide resistance management - Xiaoqi Wang; Peng Song; Boyang An; Guy Smagghe; Shipeng Han; Shanshan Feng; Qiuju Qin; Da Wang; Yunzhuan He (Pesticide Biochemistry and Physiology, 2026)

Modulation of protein self-assembly via hydrolysis and metal ion coordination: Effects on EGCG encapsulation and controlled release - Qian-Da Xu; Qiang He; Wei-Cai Zeng (Food Chemistry, 2026)

Impact of food processing methods and polyphenol interactions on the structural integrity and functionality of wheat gluten proteins - Ziqi Guo; Bruna Monteiro; Sara da Silva; Daniela Milheiro; Susana Soares; Nuno Mateus; Victor Freitas; Jingren He; Ricardo Dias (Food Chemistry, 2026)

Integrated HTO@fiber interfacial evaporator for concurrent photovoltaic cooling, lithium extraction, and desalination - Qihao He; Yang Xiao; Da Li; Guangzhao Qin; Xiong Zheng (Desalination, 2026)

Mechanoadaptive conductive hydrogels with dual functionalities for epidermal sEMG monitoring and diabetic wound healing - Guoqiang Ren; Jingyun Ma; Qiuyue Peng; Pengfei Liu; Xiaobo Wang; Da Li; Yuesheng Zhang; Chaonan He; Chen Huang; Honghua Ye; Yavuz Nuri Ertas; Qingbo Xu; et al. (Chemical Engineering Journal, 2026)

Predatory performances and adaptive strategies of Eocanthecona furcellata (Hemiptera: Pentatomidae) to the larvae of Phauda flammans (Lepidoptera: Phaudidae) - Jian-Zhong Ning; Da-Xing Lu; Xiong Zhao He; Xiao-Yun Wang; Kai Lin; Jun Li; Xia-Lin Zheng (Applied Animal Behaviour Science, 2026)

A Novel Self-Adaptive Marine Current Turbine with a Magnetically Driven Speed-Increasing Seal - Futian Geng; Xiao Zhang; Yanhui Wang; Yinghao Dang; Zongyang He; Guanzheng Xu; Da Che; Siyu Zhang; Baigong Wu; Wanqiang Zhu (Journal of Marine Science and Engineering, 2026)
This study presents a novel self-adaptive marine current power generation system capable of operating efficiently across a wide range of flow velocities. The key innovations include an adaptive variable-solidity rotor and a non-contact magnetic speed-increasing dynamic seal. The rotor employs foldable blades that enable passive solidity regulation in response to varying inflow conditions. At low flow velocities, the blades remain deployed, increasing rotor solidity and reducing the required startup flow velocity. Water tank experiments indicate that the minimum startup velocity of the variable-solidity rotor is 0.217 m/s, which represents a 38% reduction compared to a conventional rotor. At high flow velocities, the blades fold under increased hydrodynamic loading, thereby reducing the effective solidity and suppressing torque growth to provide overload protection. The power transmission module incorporates a non-contact magnetic speed-increasing dynamic seal, which ensures underwater dynamic sealing of the main shaft while simultaneously increasing the rotational speed of the driven shaft. Motor-driven bench tests demonstrate that when the active shaft speed remains below the cut-off threshold, a stable speed-increasing ratio of 2:1 is maintained, enabling effective speed amplification and torque transmission. Once the active shaft speed exceeds the cut-off threshold, the driven shaft automatically stalls, thereby preventing motor overload. Overall, this work provides an effective solution for enhancing the operational adaptability and transmission reliability of marine current energy conversion systems under variable flow conditions.

In situ amidation of NH3 in biogas on sludge-derived carbon to promote coexisting CO2 adsorption - Zhangliang Han; Aoran Zhang; Shuofei Yuan; Xinyue Lu; Shuangxi Fang; Juntao Tang; Da Wang; Zhiqiao He; Feilong Dong; Shuang Song (Water Research, 2026)

Study on the dynamic characteristics of thermal oxidation deposition of aviation kerosene in variable cross-section channels - Xuanyang Zou; Jiali Yang; Huaizhi Han; Da He (Fuel, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

Boron and oxygen isotopes fractionation between borate minerals and fluids and implications for borate deposit formation - Da-Sheng Zuo; Hai-Zhen Wei; Jian-Jun Lu; M.R. Palmer; A.E. Williams-Jones; Jun-Lin Wang; Shao-Yong Jiang; Ke Yang; He-Feng Lin; Simon V. Hohl; Yi-Chu Chen (Applied Geochemistry, 2026)

Tree Diversity Enhances Nitrogen Retention and Accelerates Phosphorus Cycling - Tao Wang; Zaipeng Yu; Minghui Da; Mengjuan Wang; Hui Jia; Lulu He; Xiaohua Wan; Zhiqun Huang; Yann Hautier (Global Change Biology, 2026)
Nitrogen (N) and phosphorus (P) cycling are crucial for terrestrial ecosystem productivity and carbon sequestration. While biodiversity is known to regulate soil N and P availability, the mechanistic linkages between biodiversity and fundamental processes of nutrient cycles remain unclear. This knowledge gap limits our capacity to model ecosystem biogeochemical responses to biodiversity loss. Using a large‐scale tree diversity experiment in subtropical China, we examined how tree species richness regulates ecosystem nutrient cycling in a region with N sufficiency but P limitation. We found that increased tree species richness enhanced N retention by boosting plant N stock and recycling, while reducing soil NO 3 − leaching and N 2 O emissions. These shifts, coupled with a reduction in soil δ 15 N, demonstrate tighter N cycling. Concurrently, tree species richness increased soil acid phosphatase activity, foliar P resorption efficiency, and plant P storage, synergistically accelerating ecosystem P cycling. Our integrated findings provide direct experimental evidence that tree diversity regulates both N and P cycling, offering valuable insights into how plant diversity can mitigate nutrient imbalances and promote ecosystem resilience to nutrient limitations.

Efficacy of copper alloy coatings in controlling Ichthyophthirius multifiliis infections: a sustainable alternative for freshwater aquaculture - Zi-Hong Guo; Wen-Hao Wu; Ming-Da Chen; Zi-Jian Long; Jian-Cheng He; Jia-Hao Zhang; You-Lu Su; Biao Jiang (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

A modified soil arching model for pile-supported embankments: integrating cohesive fill and geosynthetic membrane effects - Xin Wang; Guang qing Yang; Chen Qiao; Da Zhang; He Wang; Zhi Jie Wang; Jun Wang (Transportation Geotechnics, 2026)

Quantitative prediction of fracture distribution in deep conglomerate reservoirs of the Bozhong 19-6 South structure, offshore Bohai Bay Basin, East China: Insights from numerical simulation of multiphase strike-slip regimes - Liang Zhou; Chao Deng; Li-ya Da; Yu Xia; He-wei Hu; Kai Ji; Chang-yu Fan; Yong Cheng; Yu-jie Ning; Xiao-fang Yang (Marine and Petroleum Geology, 2026)

Spatiotemporal prediction of transportation hub passenger distribution with sparse observation data: A pedestrian dynamics-informed deep learning approach - Shulin He; Xinran Ju; Wendong Chen; Da Lei (Journal of Transport Geography, 2026)

Dual protein-cyclodextrin carriers regulated by metal ions and tannic acid for encapsulation and functional protection of lycopene - Qian-Da Xu; Zhi-Long Yu; Qiang He; Wei-Cai Zeng (Food Research International, 2026)

Regulated cell death in endometrial diseases: from molecular mechanisms to targeted therapies - Duo Zi; Jing Sun; Na Zuo; Tingting Li; Junzhi Liang; Jia Hu; Zhijing Na; Hao Zhang; Lixia He; Da Li (Archives of Toxicology, 2026)

Boosting the electro-Fenton process with a functionalized ACF cathode: Simultaneous H2O2 production and Fe2 + regeneration for rapid bisphenol A degradation - Juntao Tang; Yuhao Wu; Guanlong Wang; Mengyi Cao; Junxi Song; Da Wang; Weiting Yu; Yan Yu; Zhiqiao He; Shuang Song (Journal of Environmental Chemical Engineering, 2025)

Spermidine enhances cold tolerance in tomato fruit by boosting antioxidant and energy metabolism synergy - Jian-Lin He; Shi-Yin Xie; Xiao-Dan Zhao; Da-Qi Fu (Food Research International, 2025)

The inhibitory mechanisms of plasma-activated water on biofilm formation of Pseudomonas fluorescens by disrupting quorum sensing - Yi-Ming Zhao; Lin Zhang; Yulong Bao; Yiting Guo; Haile Ma; Ronghai He; Paula Bourke; Da-Wen Sun (Food Research International, 2025)

Myocardial-targeted mitochondria attenuate ischemic/reperfusion injury by reprogramming oxidative phosphorylation and modulating pyroptosis - Xi Li; Maodi Xie; Da Zhu; Qinqin He; Guo Chen; Zhongxiu Chen; Qian Li; Tao Li (Chemical Engineering Journal, 2025)

Corrigendum to “Evaluation of bacteriostatic and antioxidant screening of secondary metabolites of endophytic fungi in Lanzhou lily” [Bioresour. Technol. Rep. 32 (2025) 102380] - Xinlan Wang; Bolu Sun; Ying Lv; Miao Zhou; Xuanxiu Da; Jiali Kang; Haiying He; Chenyu Qin; Quhuan Ma; Hongxia Shi; Lin Yang; Xiaofeng Shi (Bioresource Technology Reports, 2025)

Evaluation of bacteriostatic and antioxidant screening of secondary metabolites of endophytic fungi in Lanzhou lily - Xinlan Wang; Bolu Sun; Ying Lv; Miao Zhou; Xuanxiu Da; Jiali Kang; Haiying He; Chenyu Qin; Quhuan Ma; Hongxia Shi; Lin Yang; Xiaofeng Shi (Bioresource Technology Reports, 2025)

Periodontitis, subclinical myocardial injury, and cardiovascular mortality among US adults: a population-based study - Da-Chuan Guo; Wan-Bing He; Zhi-Teng Chen; Jing-Feng Wang; Tao Shen; Hai-Feng Zhang; De-Ping Liu (Inflammation Research, 2025)

Space-time explainable modelling of regional hillslope deformation, an example from the Tibetan Plateau - Jun He; Hakan Tanyas; Da Huang; Luigi Lombardo (Remote Sensing of Environment, 2025)

Improvement of RNAi efficiency by delivering of dsRNA formulated with cell-penetrating disulfide polymer in the fall Armyworm, Spodoptera frugiperda - Xu Wu; Wen-Mei Li; Qiang Xu; Xiao-Ping Yi; Da-He Zhang; Ming-Zhe He; Yu-Hong Ren (Journal of Insect Physiology, 2025)

Characterisation of dynamic changes in nutritional components and aroma compound formation in natto during fermentation and post-ripening - Mubai Sun; Ni Yang; Yuguang He; Xinyu Miao; Honghong Niu; Mei Hua; Jinghui Wang; Da Li (Food Research International, 2025)

A dynamic prediction model for maximum lateral displacement of foundation pit enclosure structure using multi-source fusion method - He Wei Kuang; Zhi Yong Ai; Gan Lin Gu; Hong Wei Huang; Zeng Zhi Qian; Da Xing Zhou; Yu Xin Zhai; Hai Feng Guo (Computers and Geotechnics, 2025)

Polyimide porous thermoelectric fibers based on sheath core structure: A new self-powered material for early fire warning and flame retardant protection - Xinbin Ji; Yulong Xiang; Jing Guo; Fucheng Guan; Da Bao; Qiang Yang; Zheng Li; Yihang Zhang; Xin Zhang; Jiahao He (Chemical Engineering Journal, 2025)

Joint optimization of dynamic berth allocation and energy supply for USVs based on an improved PSO algorithm - Jiming Zhang; Yang Long; Jiao Deng; Zhongjie He; Da Qiu; Song Liu (Ocean Engineering, 2025)

OsSPT38 encodes a novel SUMO E3 ligase that improves rice stress resilience and grain yield - Zi-Sheng Zhang; Zheng-Yi Zhang; Jin-Qiu Xia; Si-Yan Chen; Liang-Qi Sun; Jie Wu; Da-Yu He; Jing-Xian Wang; Qin-Yu Liang; Lei Wang; Ke Ruan; Tian Sang; et al. (Molecular Plant, 2025)

Separation and recovery of vanadium from leaching solution of calcium roasting vanadium slag by extraction with P204 extractant - Da-long Wang; Lin Zhang; Jing-wei Li; Chen Chen; Yin-he Lin; Zhi Yang; Da-ya Wang; Huan-jian Hou; Jian Chen; Tang-jie Zhou; Wen-ming Tang (Minerals Engineering, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

Smart construction of 8N-CuO for efficient peroxymonosulfate (PMS) activation: The synergistic effect of 8N-CuO-induced non-radical/radical pathways - Linglong Shi; Da Li; Shuangzhen Guo; Lihong Zhang; Jiaxin Bai; Mengqi Li; Sizhe Peng; Meiqi He; Yan Li; Yu Liu (Journal of Environmental Chemical Engineering, 2025)

Specific dual-mode fluorometric and colorimetric detection of nitrite based on oxidase-like activity of carbon dots/iron alkoxide composite - Dingfeng Wang; Liwei Gao; Xinru Liu; Linfan Wang; Ting Zhang; Guoqiang Guo; Hongxing He; Da Chen (Food Chemistry, 2025)

Mechanical response of tunnel surrounding rock under blasting disturbance with different stress conditions based on acoustic emission and digital image correlation - Tian-xiao Chen; Shi-da Xu; Ben-guo He; Yuan-hui Li; Han Lei (Engineering Geology, 2025)

Eco-friendly eugenol curing agent-derived biobased epoxy resins for multi-functional integration - Zhiyong Li; Xiangyan Ji; Xiaoge Li; Da Gao; Lei Shen; Wei He; Jie Sun; Dingqiang Lu; Jingjing Meng; Kai Guo (Chemical Engineering Journal, 2025)

Engineering hypo-osmotic Crypthecodinium cohnii via SL-ALE for high-yield DHA biosynthesis from agricultural byproducts - Yi-Tong Yao; Yu-He Zhang; Yan Huang; Xiao Zhang; Chen-Yu Wang; Jia-Qi Zheng; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Algal Research, 2025)

Chlorella vulgaris-derived biochar loaded with nano zero-valent iron induces different responses in algal cells in terms of growth, physiological, antioxidant defense, and biochemical indices - Guoming Zeng; Zilong Ma; Yu He; Qian Luo; Qiaoli Xie; Da Sun (Algal Research, 2025)

Optimizing removal and control of inclusions/impurities and recovery of valuable elements in metallurgical melts via electric field: toward circular economy and resource efficiency - Wen-zhi Xia; Hai-chuan Wang; Ruipeng Pang; Yun Zhou; Zhi-you Liao; Ting Wu; Baowen He; Guang-da Bao; Zhen Hou; Shao-long Chu; Ping-fan Ren (Chemical Engineering Journal, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

Dual-defect engineering strategy induced polarization loss in trimetallic MOFs/MXene-derived nanocomposites for broadening microwave absorption bandwidth - Yuanzhao Hou; Binchuan Li; Kuiren Liu; Jianshe Chen; Yongfeng Chang; Bo Wang; Shicheng Wei; Xiaocai He; Da Li; Chul B. Park; Daxue Fu; Qing Han (Chemical Engineering Journal, 2025)

Screening of biocontrol agents against lily bulb rot caused by F. oxysporum and research on their fermentation process - Bolu Sun; Xinlan Wang; Ying Lv; Xuanxiu Da; Miao Zhou; Jiali Kang; Haiying He; Chenyu Qin; Xiangdong Wang; Lin Yang; Quhuan Ma; Hongxia Shi; et al. (Bioresource Technology Reports, 2025)

Climate and grazing effects on productivity allocation in alpine grasslands of the Qinghai-Tibet Plateau - Zhaomin Zhang; Ben Niu; Xianzhou Zhang; Yongtao He; Xiaoli Zhou; Da Wei (Agricultural and Forest Meteorology, 2025)

Efficient catalytic degradation and detoxification of 6PPD-quinone by the multifunctional enzyme system of phanerochaete chrysosporium - Haiyang Yu; Li Luo; Baihui Wu; Jiaxuan He; Hanbing Wang; Rongbing Chen; Mingxia Ji; Qinsi Yang; Guoming Zeng; Wei Wu; Da Sun (Journal of Hazardous Materials, 2025)

Mechanism of electrochemical algal control and its effect on metabolic pathways of algal cells - Guoming Zeng; Zilong Ma; Rui Zhang; Yu He; Yong Xiao; Da Sun; Xiaoling Lei (Journal of Hazardous Materials, 2025)

Simulating the effects on carbon sinks caused by urban expansion using a coupled urban–ecological model - Yida Wang; Da Zhang; Chunyang He; Tao Qi; Penghui Li (Journal of Cleaner Production, 2025)

Portable and miniature sensors in supply chain for food authentication: a review - Hong-Ju He; Marcus Vinicius da Silva Ferreira; Qianyi Wu; Hamed Karami; Mohammed Kamruzzaman (Critical Reviews in Food Science and Nutrition, 2025)

Phosphoproteomics reveals essential regulatory roles of phosphorylation in marine oligotrophic bacteria - Yu Zhang; Yao-Hui He; Zhang-Xian Xie; Zhuo-An Bai; Guo-Sheng Hu; Ming-Hua Wang; Stephen J. Giovannoni; Da-Zhi Wang (Marine Life Science & Technology, 2025)
Oligotrophic bacteria with reduced genomes have relatively few transcriptional regulators and are thought to rely more than other bacteria on post-transcriptional regulation to respond to environmental stimuli. SAR11 bacteria are the most abundant group of heterotrophic bacteria in marine planktonic systems and are a model for understanding genome reduction in other free-living microorganisms. Here, we report a comprehensive, quantitative protein phosphorylation profile for SAR11 strain HTCC1062 grown under various environmentally relevant conditions, including light/dark cycles, temperature differences, and nutrient limitations, to investigate phosphorylation dynamics in this streamlined organism. Nearly half of proteins encoded by the genome were detected in phosphorylated forms under at least one condition. 1014 Ser/Thr/Tyr phosphorylation sites were observed in 1576 phosphopeptides from 555 phosphoproteins. Protein phosphorylation was concentrated in proteins for functions associated with nutrient acquisition and growth, such as ABC transporters, RNA polymerase, and ribosomal proteins. Prominent patterns in protein phosphorylation were detected across a range of culture conditions. In these cells, which previously have been shown to continuously express nearly their entire proteome, protein phosphorylation was more dynamic than protein abundance, supporting the hypothesis that post-transcriptional regulation by protein phosphorylation might play a large role in modulating protein activity. Our findings support a regulatory model characterized by minimal variation in protein expression but extensive protein phosphorylation. This model diverges from bacterial regulatory paradigms reliant on transcriptional control, and may be relevant to understanding other abundant heterotrophs with reduced genomes.

Wheat bran supplementation improved polystyrene degradation efficiency of Zophobas atratus larvae by alleviating intestinal injury caused by polystyrene-intake - Cong Liang; Yun Jia; Ren-tao He; Bin Ding; Zheng-da Yang; Xiao-qiang Cao; Jian Zhang (Journal of Hazardous Materials, 2025)

Acid-engineered UiO-66(Ce): From the limitations of concealed MOF sites to catalytic excellence for rapid atrazine degradation - Da Wang; Yufeng Ying; Liwen Cai; Haijun Cheng; Stefanos Giannakis; Gholamreza Moussavi; Zhiqiao He; Shuang Song; Jun Ma (Chemical Engineering Journal, 2025)

Recycling and regenerating of spent ternary cathode in lithium-ion battery via the corn straw-induced thermal reduction - Bingen Yuan; Xuzhuyan Ma; Xin Zhang; Jiafang Jian; Chenxia Wang; Qin Wang; Liusheng Xiao; Chunfei Zhang; Lan Xia; Da Zheng; Jianxin Wang; He Miao; et al. (Waste Management, 2025)

Visual-language reasoning segmentation (LARSE) of function-level building footprint across Yangtze River Economic Belt of China - Da He; Xiaoping Liu; Qian Shi; Yue Zheng (Sustainable Cities and Society, 2025)

Identification of novel sulfur-containing petroporphyrins in a natural bitumen: Potential biomarkers for aerobic organisms - Fang Zheng; Weisheng Yang; Yanbin Wang; Mi An; Da Huo; Chunyan Wang; Qing Cao; Jing He; Quan Shi; Yongge Sun (Organic Geochemistry, 2025)

Three-dimensional aligned wood arrays loading with metal-organic frameworks for improved radionuclides removal - Yifan Yan; ChuanYing Wu; Qiang Guan; Da Tian; Dichen Xia; Yue He; Pengcheng Gu (Journal of Environmental Chemical Engineering, 2025)

Nanoparticle contrast agent Mn3O4/SiO2/C as an ozonation catalyst with unexpected synergy in degrading organic contrast agent iopamidol: an effective “treat-waste-with-waste” strategy for medical wastewater - Wen Xu; Shiwen Dong; Haijun Cheng; Stefanos Giannakis; Xiaohui Lu; Zhiqiao He; Da Wang; Shuang Song; Jun Ma (Chemical Engineering Journal, 2025)

Modulation of Intestinal Flora: a Novel Immunotherapeutic Approach for Enhancing Thyroid Cancer Treatment - Weiqiang Huang; Tao Jiang; Jiaxuan He; Jing Ruan; Baihui Wu; Runchao Tao; Peiye Xu; Yongpan Wang; Rongbing Chen; Hanbing Wang; Qinsi Yang; Kun Zhang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Unveiling novel oxygen-dependent docosahexaenoic acid biosynthesis pathway in Crypthecodinium cohnii via dual-function △4-fatty acid desaturases - Yi-Tong Yao; Xiao Zhang; Chen-Yu Wang; Yu-He Zhang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Bioresource Technology, 2025)

Performance of cut-off walls under long-term vacuum suction: A case study - Chenchen Xu; Yongtao Hu; Shijie Han; Geng Xueyu; Da Cheng; Ning He; Yongfeng Deng (Marine Georesources & Geotechnology, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Exploring the epigenetic impacts of atrazine in zebrafish: Unveiling mechanisms of neurotoxicity, reproductive toxicity, and implications for human health - Haiyang Yu; Baihui Wu; Jiaxuan He; Jia Yi; Wei Wu; Hanbing Wang; Qinsi Yang; Da Sun; Hongliang Zheng (Environmental Pollution, 2025)

Strong, flame-retardant, and smoke-suppressive green composites enabled by a simple and effective synergistic mineralization strategy - Shenghui Lai; Jing Liu; Tao Yang; Jinzhuo Huang; Yinghe Wang; Zebin Deng; Da Liu; Guangming Yuan; Shuaiming He (Chemical Engineering Journal, 2025)

Cooling and Exhumation of the Late Cretaceous Laojunshan Granites in Southeast Yunnan Province, China: Constraints from Fission-Track Thermochronology and Tectonic Implications - Fang Li; Hao Bai; Ye Fang; Da Zhang; Ganguo Wu; Wei Xue; Chaoyang Que; Xinming Zhang; Xiaolong He; Bojie Hu (Journal of Earth Science, 2025)

Object detection with attribute tagging task: Model design and evaluation on agricultural datasets - Da Liu; Pengguang He; Qingyu Wang; Yingchao He; Fang Cheng (Computers and Electronics in Agriculture, 2025)

Glacial hazards change in Xinjiang over the past seven decades: Spatiotemporal patterns and trends - Meixia Wang; Donghui Shangguan; Da Li; Yaojun Li; Rongjun Wang; Rui He; Asim Qayyum Butt (Quaternary Science Reviews, 2025)

PSLSA v2.0: An automatic Python package integrating machine learning models for regional landslide susceptibility assessment - Zizheng Guo; Haojie Wang; Jun He; Da Huang; Yixiang Song; Tengfei Wang; Yuanbo Liu; Joaquin V. Ferrer (Environmental Modelling & Software, 2025)

Unraveling phase-dependent variations of viral community, virus-host linkage, and functional potential during manure composting process - Zhengyuan Zhou; Songfeng Liu; Muhammad Saleem; Fei Liu; Ruiwen Hu; Hualong Su; Da Dong; Zhiwen Luo; Yongjie Wu; Yan Zhang; Zhili He; Cheng Wang (Bioresource Technology, 2025)

Functional microorganisms in hydrogen production: Mechanisms and applications - Yonghong Fan; Feiran Zhang; Kun He; Dan Yu; Haoming Chen; Da Tian; Yixiao Shi; Zhen Li; Xiaomei Wang (Bioresource Technology, 2025)

Spatial prediction of InSAR-derived hillslope velocities via deep learning - Jun He; Hakan Tanyas; Ashok Dahal; Da Huang; Luigi Lombardo (Bulletin of Engineering Geology and the Environment, 2025)
Spatiotemporal patterns of earth surface deformation are influenced by a combination of static and dynamic environmental characteristics specific to any landscape of interest. Nowadays, these patterns can be captured for larger areas using Interferometric Synthetic-Aperture Radar (InSAR) technologies and yet, their spatial prediction has been poorly investigated so far. Here, we initially compute the InSAR-derived line-of-sight hillslope velocities (V LOS ) and calculate their mean (ranging from 0 to ~ 30 mm/y) and maximum (ranging from 0 to ~ 60 mm/y) values per Slope Units (SUs). These separately constitute the response variables to be modelled through a series of deep learning routines: i ) a basic neural network (Multi-Layer Perceptron), ii ) a Graph Convolutional Network implemented to capture spatial dependence among neighbouring SUs, and iii ) an Edge-Featured Graph Attention Network sensitive not only to the interdependence brought by the SU positions in space but also to reciprocal terrain characteristics. We assessed the model performance for both models via Mean Absolute Error (MAE), r-squared (R 2 ), and Pearson Correlation Coefficient (PCC). The Edge-Featured Graph Attention Network model produced the best performance. The result for the first model targeting the mean V LOS are 4.75 mm/y, 0.63, and 0.79 for MAE, R 2 , and PCC, respectively. As for the second model, targeting the maximum V LOS , these are 19.52 mm/y, 0.55 and 0.75. We also showcased interpretable multivariate models, where the contribution of each predictor to the InSAR velocities is summarized and interpreted. This represent a clear example where InSAR-derived hillslope velocities are accurately estimated at regional scales, thus setting up the scene for further advances towards space-time regional deformation modelling.

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Temporal and spatial changes of glacial lakes in the central Himalayas and their response to climate change based on multi-source remote sensing data - Xiaoqiang Cheng; Donghui Shangguan; Chengsheng Yang; Wangping Li; Zhaoye Zhou; Xiaojie Liu; Da Li; Xiuxia Zhang; Huilan Ding; Zewei Liu; Yi Yu; Xiaoxian Wang; et al. (Global and Planetary Change, 2025)

Experimental analysis and optimization of the variable valve timing on attaining high efficiency with low NOx emission of a direct-injected hydrogen engine - Feng-yu Lai; Bai-gang Sun; Shi-wei Zhang; Kang-da Wang; Qing-he Luo; Ling-zhi Bao; Felix Leach (Fuel, 2025)

Leveraging zebrafish models for advancing radiobiology: Mechanisms, applications, and future prospects in radiation exposure research - Ting Xu; Fan Liu; Jiaxuan He; Peiye Xu; Junying Qu; Hanbing Wang; Jinghui Yue; Qinsi Yang; Wei Wu; Guoming Zeng; Da Sun; Xia Chen (Environmental Research, 2025)

Controllable supramolecular self-assembly of proteins mediated by metal-polyphenols: Characteristics and their applications on encapsulating hydrophobic small molecules - Qian-Da Xu; Zhi-Long Yu; Qiang He; Wei-Cai Zeng (Chemical Engineering Journal, 2025)

The Role of the Intestinal Flora and Its Derivatives in Neurocognitive Disorders: A Narrative Review from Surgical Perspective - Jian Huang; Tian-Shou Qin; Yun Bo; Yu-Jin Li; Rong-Sheng Liu; Yang Yu; Xiao-Dong Li; Jin-Can He; Ai-Xin Ma; Da-Peng Tao; Wen-Jun Ren; Jun Peng (Molecular Neurobiology, 2025)
Perioperative neurocognitive dysfunction is a significant concern for population health, impacting postoperative recovery and increasing the financial burden on patients. With an increasing number of surgical procedures being performed, the prevention and management of perioperative neurocognitive dysfunction have garnered significant attention. While factors such as age, lifestyle, genetics, and education are known to influence the development of cognitive dysfunction, recent research has highlighted the role of the gut microbiota in neurological health. An increased abundance of pro-inflammatory gut microbiota can trigger and worsen neuroinflammation, neuronal cell damage, and impaired cellular autophagy. Moreover, the inflammation-promoting gut microbiota can disrupt immune function, impair neuroautophagy, and affect the production and circulation of extracellular vesicles and neurotransmitters. These factors collectively play a role in the onset and advancement of cognitive impairment. This narrative review delves into the molecular mechanisms through which gut microbiota and their derivatives contribute to cognitive impairment, focusing on the impact of anesthesia surgery, changes in gut microbial populations, and perioperative cognitive impairment associations. The study suggests that alterations in the abundance of various bacterial species and their metabolites pre- and post-surgery may be linked to postoperative cognitive impairment. Furthermore, the potential of probiotics or prebiotics in addressing cognitive impairment is discussed, offering a promising avenue for investigating the treatment of perioperative neurocognitive disorders.

Ferric ammonium citrate regulates iron death in mature porcine oocytes and their embryonic development in vitro through the NRF2 signaling pathway - Da Xu; Caifei Li; Yao Huang; Kaixin Hu; Cheng Wang; Pengyang Zhou; Haiying Shen; Chang Liu; Jiatong Xu; Jinyuan He; Jiaxu Jiang; Qi Qi; et al. (Theriogenology, 2025)

Dynamic analysis of green technology innovation in products and processes under supply chain competition scenarios—A study based on stochastic differential game model - Rui Sun; Da-yi He; Jing-jing Yan (Journal of Environmental Management, 2025)

Metagenomic perspectives on antibiotic resistance genes in tap water: The environmental characteristic, potential mobility and health threat - Qiyue Meng; Yibo Zhang; Da He; Yu Xia; Jie Fu; Chenyuan Dang (Journal of Environmental Sciences, 2025)

Ultrasound-Targeted β-Catenin Gene Therapy Improves the Cardiac Function in Mice After Myocardial Infarction - Lei Yang; Tong Gao; Yu Huang; Pei-he Wang; Xin-hao Han; Jie Wu; Lei Huang; Qing-en Da; Kun-fu Ouyang; Zhen Han; Hai Tian; Lu Sun (Cardiovascular Toxicology, 2025)

Niche Partitioning and Intraspecific Variation of Thaumarchaeota in Deep Ocean Sediments - Ronghua Liu; Xinxin He; Gaoyang Ren; Da‐Wei Li; Meixun Zhao; Laura Lehtovirta‐Morley; Jonathan D. Todd; Xiao‐Hua Zhang; Jiwen Liu (Environmental Microbiology, 2025)
Deep‐sea sediments contain a large number of Thaumarchaeota that are phylogenetically distinct from their pelagic counterparts. However, their ecology and evolutionary adaptations are not well understood. Metagenomic analyses were conducted on samples from various depths of a 750‐cm sediment core collected from the Mariana Trench Challenger Deep. The abundance of Thaumarchaeota and archaeal amoA generally decreased with depth, except for an unexpected peak midway through the core. The thaumarchaeotal metagenome‐assembled genomes were classified into diverse phylogenetic clusters associated with amoA ‐NP‐γ, amoA ‐NP‐θ, and amoA ‐NP‐δ of ammonia‐oxidising Thaumarchaeota and non‐ammonia‐oxidising lineages. The most abundant group was within amoA ‐NP‐γ, which is usually found in coastal and shallow habitats, indicating potential niche expansion from marine shallow to hadal environments. This benthic group showed within‐species genomic variations compared to the previously identified Hadal water group, suggesting microdiversification of hadal Thaumarchaeota along with niche separation between benthic and pelagic environments. Evolutionary adaptations associated with the benthic‐to‐pelagic transition included reduced genome size, loss of motility/cell adhesion, altered energy metabolism, and different mechanisms for substrate acquisition and regulation (e.g., ammonium). These findings offer new insights into the evolution of hadal Thaumarchaeota and demonstrate, for the first time, intraspecies‐level genomic variation in Thaumarchaeota related to the benthic‐versus‐pelagic niche partitioning in the deep ocean.

Autonomous net inspection and cleaning in sea-based fish farms: A review - Jiaying Fu; Da Liu; Yingchao He; Fang Cheng (Computers and Electronics in Agriculture, 2024)

Multi-omics analysis of the effects of low-temperature storage on chilling injury of bitter gourd - Hongwei Wang; Ling Li; Da-Wen Sun; Lili Ma; Lichun Han; Xuelian He; Qing Wang; Christopher B. Watkins; Jinhua Zuo; Yanyan Zheng (Postharvest Biology and Technology, 2024)

Utilizing fly ash from coal-fired power plants to improve the utilization of incineration fly ash resources and reduce toxicity - Xiaodong Ma; Tingshu He; Yongqi Da; Fuyun Su; Renhe Yang (Journal of Environmental Management, 2024)

Explore synergistic catalytic ozonation by dual active sites of oxygen vacancies and defects in MgO/biochar for atrazine degradation - Shiwen Dong; Luzhen Liu; Wen Xu; Haijun Cheng; Zhiqiao He; Feilong Dong; Da Wang; Lizhang Wang; Shuang Song; Jun Ma (Journal of Environmental Chemical Engineering, 2024)

Risk assessment of migrants released from multilayer packaging materials: Direct immersion-solid-phase microextraction coupled to gas chromatography-mass spectrometry - Weiyan Guan; Yue He; David Julian McClements; Jing Chen; Da Ma (Food Packaging and Shelf Life, 2024)

Insights into the sustainable design of engineered hydrochar co-doped with cobalt and nitrogen as peroxymonosulfate activator for fluoroquinolones removal - Ganapaty Manickavasagam; Chao He; Tao Zhou; Kun-Yi Andrew Lin; Tuan Sherwyn Hamidon; M. Hazwan Hussin; Mardiana Saaid; Wen-Da Oh (Chemical Engineering Journal, 2024)

Activated carbon fiber loaded nano zero-valent iron for Microcystis aeruginosa removal: Performance and mechanisms - Guoming Zeng; Dong Liang; Xuanhao Fan; Yu He; Rui Zhang; Xiaoling Lei; Haoxuan Wei; Da Sun (Bioresource Technology, 2024)

Association Between Neuroinflammation and Parkinson’s Disease: A Comprehensive Mendelian Randomization Study - YiNi Wang; XinYu Shi; YaPing Yin; Fei Yang; YiNan Zhang; Xin He; Da Wen; Bai-Xiang Li; Kun Ma (Molecular Neurobiology, 2024)

Dedolomitization arises the knife-like structure of dolostone: insights from the oolitic dolostone of Cambrian Zhangxia formation, North China Craton - Zhe-Xin Cai; Shan-Shan Li; Yi-Ning He; Tao Cui; Xin-Yu Wu; Hao-Cheng Yu; Zhao-Liang Hou; Yu-Tian Tao; Da Wang; Kun-Feng Qiu (Carbonates and Evaporites, 2024)

Molecular evidence of internal carbon-driven partial denitrification in a mainstream pilot A-B system coupled with side-stream EBPR treating municipal wastewater - Da Kang; Yuan Yan; IL Han; Jangho Lee; Kester McCullough; Guangyu Li; Zijian Leo Wang; Peisheng He; Dongqi Wang; Stephanie Klaus; Ping Zheng; Varun Srinivasan; et al. (Water Research, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

Hydroxylated SiO2-modified {0 0 1}-TiO2 nanosheets as a surface multifunctional photocatalyst for enhanced degradation of gaseous toluene - Juntao Tang; Xinlong Wang; Yusheng Huang; Xiaopeng Du; Zhiqiao He; Da Wang; Shuang Song (Chemical Engineering Journal, 2024)

Real-time tilapia fillet defect segmentation on edge device for robotic trimming - Yingchao He; Weidong Xu; Da Liu; Maozhen Qu; Jiaying Fu; Fang Cheng (Computers and Electronics in Agriculture, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Multiomics comprehensive analysis of pre-storage low-temperature on cowpea metabolism - Lichun Han; Zhengrong Wang; Qing Wang; Da-Wen Sun; Xuelian He; Hongwei Wang; Lili Ma; Chunmei Bai; Christopher B. Watkins; Jinhua Zuo; Yanyan Zheng (Postharvest Biology and Technology, 2024)

Experimental investigation of the matching boundary and optimization strategy of a variable geometry turbocharged direct-injected hydrogen engine - Feng-yu Lai; Bai-gang Sun; Zhi-fu Zhang; Shi-wei Zhang; Kang-da Wang; Xue-ming Ju; Qing-he Luo; Ling-zhi Bao; Felix Leach (Fuel, 2024)

Array-optimized artificial olfactory sensor enabling cost-effective and non-destructive detection of mycotoxin-contaminated maize - Maozhen Qu; Yingchao He; Weidong Xu; Da Liu; Changqing An; Shanming Liu; Guang Liu; Fang Cheng (Food Chemistry, 2024)

Immune checkpoint-regulatable hydrogel-immobilized nanotherapeutics for post-surgical treatment of osteosarcoma - Da-Wang Zhao; Zhiliang Gao; Meng Si; Rui Hu; Xue Ma; Kaiwen Liu; Yixiang Zhao; Qiting He; Xiangzhen Kong; Chunwang Jia; Haoxin Zhai; Yuanqiang Zhang; et al. (Chemical Engineering Journal, 2024)

Impact of nickel and alkaline earth metals interaction on sustainable carbon nanotubes generation from plastic face masks via catalytic pyrolysis - Xiu-Xian Lim; Siew-Chun Low; Kai Qi Tan; Kun-Yi Andrew Lin; Chao He; Tao Zhou; Wen-Da Oh (Chemical Engineering Journal, 2024)

Highly dispersed and stable Schiff base nickel catalyst on multi-walled carbon nanotubes promote ethylene oligomerization - Yang Li; Chao He; Da Song; Mingyang Fan; Lijun Guo; Xue Zhai; Feng Li; Cuiqin Li; Zhen Huang (Chemical Engineering Journal, 2024)

Dialdehyde starch cross-linked aminated gelatin sponges with excellent hemostatic performance and biocompatibility - Yu-He Zhu; Chen-Yu Zhou; Xu Peng; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Xiao-Jie Ju; Liang-Yin Chu (Carbohydrate Polymers, 2024)

Regulating iron center by defective MoS2 for superior Fenton-like catalysis in water purification: The key role of surface interaction and superoxide radical in accelerating metal redox-cycling - Ai-Yong Zhang; Zhi-Xian Lin; Jing-Yu Zhang; Ming-He Zhang; Chi Zhang; Lu Zhao; Liang Liu; Wei Da; Lyumeng Ye (Chemosphere, 2024)

Fruits’ cold tolerance: a review of mechanisms and methods - Jian-Lin He; Gang-Shuai Liu; Xiao-Dan Zhao; Lan-Ting Xiang; Shi-Yin Xie; Yun-Xiang Wang; Da-Qi Fu (Postharvest Biology and Technology, 2024)

Hydrothermal petroleum related to intracontinental magmatism in the Bohai Bay Basin, eastern China - Li Wang; Yuanjia Han; Da Lou; Zhiliang He; Xiaowen Guo; Matthew Steele-MacInnis (Marine and Petroleum Geology, 2024)

Analysis of the Relationship Between Parkinson’s Disease and Diabetic Retinopathy Based on Bioinformatics Methods - XinYu Shi; YiNi Wang; YaPing Yin; Fei Yang; YiNan Zhang; Xin He; Da Wen; Kun Ma; Bai-Xiang Li (Molecular Neurobiology, 2024)

Distributions and controlling factors of soil total nitrogen and nitrogen fractions along an altitude gradient in Qinghai-Tibet Plateau - Da Meng; Xinyu Wang; Jiayi Tang; Ning Zong; Jinjing Zhang; Nianpeng He (Journal of Soils and Sediments, 2024)

Minimization of heavy metal adsorption in struvite through effective separation and manipulation of flow field - Yazhou Wang; Jinrong Da; Yuchen Luo; Sirui He; Zuocong Tian; Ziyi Xue; Zehao Li; Xianyu Zhao; Desheng Yin; Hui Peng; Xiang Liu; Xiaoning Liu (Journal of Hazardous Materials, 2024)

Metabolomic insights into the effects of seasonal shifts on the dynamic variation of non-volatile compounds of abalone (Haliotis discus hannai) - He-He Tian; Yu-Lian Li; Xu-Song Wang; Xu-Hui Huang; Yu-Ying Zhang; Zi-Chun Zhang; Da-Yong Zhou; Lei Qin (Food Chemistry, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Multi-strategy synergistic scheme for progressive construction and optimization of non-covalent all-polysaccharide double-network hydrogels - Qiang Yang; Jing Guo; Sen Zhang; Shi Feng; Qiang Yao; Da Bao; Yi Xu; Fucheng Guan; Xin Zhang; Jiahao He (Chemical Engineering Journal, 2024)

Electrocatalytic nitrogen reduction to ammonia at low overpotentials based on tungsten carbide doped by non-precious metal single cobalt atoms - Ya Gao; Meng-Jiao Zhu; Xian-He Liu; Guo-Liang Dai; Yi-Wen Zhou; Ze-Da Meng; Li Luo; Tian Gan; Feng Chen; Yu-Yang Zhou; Wen-Wen Deng; Shou-Qing Liu (Chemical Engineering Journal, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Unraveling the relationship between aroma characteristics and lipid profile of abalone (Haliotis discus hannai) during seasonal fluctuation and thermal processing - He-He Tian; Yu-Lian Li; Xu-Song Wang; Xu-Hui Huang; Yu-Ying Zhang; Zi-Chun Zhang; Da-Yong Zhou; Lei Qin (Food Chemistry, 2024)

Establishing a novel ternary complex of soybean protein isolated-tannic acid-magnesium ion and its properties - Qian-Da Xu; Zhi-Long Yu; Qiang He; Wei-Cai Zeng (Food Chemistry, 2024)

Recent advances in catalyst design, performance, and challenges of metal-heteroatom-co-doped biochar as peroxymonosulfate activator for environmental remediation - Ganapaty Manickavasagam; Chao He; Kun-Yi Andrew Lin; Mardiana Saaid; Wen-Da Oh (Environmental Research, 2024)

An improved representative of stomatal models for predicting diurnal stomatal conductance at low irradiance and vapor pressure deficit in tropical rainforest trees - Wei Xue; Xue-min He; Quan Wang; Pei-jun Shi; Guang-hui Lv; Jian-feng Huang; Da Yang; Jiao-lin Zhang (Agricultural and Forest Meteorology, 2024)

Association between outdoor air pollutants and risk of acute exacerbation of chronic obstructive pulmonary disease in Xi’an, China - Xinping Fan; Xueyan Jie; Fan Zou; Dan Wang; Hongju Da; Hongxin Li; Hongyan Zhao; Jin He; Jianghao Liu; Yiyi Lu; Yun Liu (Air Quality, Atmosphere & Health, 2024)

Establishing quality evaluation standards for pomelo fruit: The role of harvesting time and appearance characteristic - Xiaojun Yan; Muhammad Atif Muneer; Mengting Qin; Jie Ou; Xiaohui Chen; Zhiyuan He; Yedong Liu; Zhihan Cheng; Da Su; Rongrong Liu; Liangquan Wu (Postharvest Biology and Technology, 2024)

Enhancing hydrochar production and mitigating heavy metal risks in sewage sludge: The role of ultrasonic pretreatment in hydrothermal carbonization - Chenyu Wang; Weibo Sun; Chao He; Xiaolong Ling; Xiaojun Zuo; Wen-Da Oh; Chaoyue Wu; Houhu Zhang (Journal of Environmental Chemical Engineering, 2024)

Cell-excreted proteins mediate the interactions of differently sized silica nanoparticles during cellular uptake - Bin Huang; Jia-Ming Li; Xiao-Mei Zang; Mei Wang; Wei Pan; Ke-Da Zhang; Huan He; Qiao-Guo Tan; Ai-Jun Miao (Journal of Hazardous Materials, 2024)

Genesis of the Haidewula volcanic rock-hosted uranium deposit in the East Kunlun Orogen, northwestern China - Kai-Xing Wang; Kun-He Zhu; Jia-Wen Dai; Jian-Jun Yang; Xiao-Dong Liu; Michel Cuney; Chi-Da Yu; Jia Wu (Journal of Asian Earth Sciences, 2024)

Micro-structure change and crystal-structure modulated of oxygen carriers for chemical looping: Controlling local chemical environment of lattice oxygen - Da Song; Tao Long; Cuiqin Li; Yang Li; Mingyang Fan; Yonghao Lu; Yuchao Zhou; Haitao Chen; Yan Lin; Zhen Huang; Fang He (Fuel, 2024)

Microcystin-RR promote lipid accumulation through CD36 mediated signal pathway and fatty acid uptake in HepG2 cells - Wenjuan Jia; Lin Zhong; Qingmiao Ren; Da Teng; Lei Gong; Haibin Dong; Jun Li; Chunxiao Wang; Yong-Xing He; Jun Yang (Environmental Research, 2024)

Mechanical Responses of a Porous Red Sandstone to Quasi-Static Cyclic Loads Under Uniaxial Compression - Zhao-Qiang Zheng; Huai-Zhong Liu; Hong-Qiang Xie; Jiang-Da He; Ming-Li Xiao; Li Zhuo (Rock Mechanics and Rock Engineering, 2024)

The earliest evidence for a microblade adaptation in the remote, high altitude regions of the Tibetan Plateau - Yingshuai Jin; Xiaoling Zhang; Shejiang Wang; Junyi Ge; Wei He; Wa Da; Yunyao Tan; Ziyi Yang; Christopher Morgan; Xing Gao (Science China Earth Sciences, 2024)

Thalassinoides ichnofabrics from the Zhangxia Formation (Cambiran Miaolingian series) in Henan province: Bioturbators as Ecosystem engineers - Bingchen Liu; Yong'an Qi; Min Wang; Wenyi He; Yaogang Du; Da Li; Mingyue Dai (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

2D Bi2MoO6 nanosheets immobilized on electrospun 1D LaFeO3 hollow nanofibers: An efficacious direct Z-scheme p-n type heterojunction photocatalyst for removal of organic contaminants under visible-light irradiation - Da Xu; Feng Sun; Feng Liu; Hong Shao; Wurigamula He; Lili Wang; Qianli Ma; Wensheng Yu; Hui Yu; Xiangting Dong (Journal of Environmental Chemical Engineering, 2024)

Ce-UiO-66-F4-based composites decorated with green carbon dots for universal adsorption of organic pollutants containing hydrogen bond donors and its application exploration - Maozhen Qu; Hengjie Yu; Yingchao He; Weidong Xu; Da Liu; Fang Cheng (Chemical Engineering Journal, 2024)

Binary Li/Na tungstates modified Mg6MnO8 as redox catalysts for enhanced performance of chemical looping oxidative dehydrogenation of ethane - Haitao Chen; Zifan Xing; Da Song; Xiang Yu; Yang Li; Fang He (Chemical Engineering Journal, 2024)

The burgeoning importance of PIWI-interacting RNAs in cancer progression - Xinpei Deng; Tianle Liao; Jindong Xie; Da Kang; Yiwei He; Yuying Sun; Zhangling Wang; Yongluo Jiang; Xuan Miao; Yixuan Yan; Hailin Tang; Lewei Zhu; et al. (Science China Life Sciences, 2024)

Revisiting the role of Acinetobacter spp. in side-stream enhanced biological phosphorus removal (S2EBPR) systems - Yuan Yan; IL Han; Jangho Lee; Guangyu Li; Varun Srinivasan; Kester McCullough; Stephanie Klaus; Da Kang; Dongqi Wang; Peisheng He; Anand Patel; Charles Bott; et al. (Water Research, 2024)

Investigation analysis of the acute asthma risk factor and phenotype based on relational analysis with outdoor air pollutants in Xi’an, China - Yiyi Lu; Xueyan Jie; Fan Zou; Dan Wang; Hongju Da; Hongxin Li; Hongyan Zhao; Jin He; Jianghao Liu; Xinping Fan; Yun Liu (Environmental Geochemistry and Health, 2024)

Ferric uptake regulator (fur) affects the pathogenicity of Aeromonas veronii TH0426 by regulating flagellar assembly and biofilm formation - Jin-shuo Gong; Ying-da Wang; Yan-long Jiang; Di Zhang; Ya-nan Cai; Xiao-feng Shan; He Gong; Hao Dong (Aquaculture, 2024)

Triclocarban exhibits higher adipogenic activity than triclosan through peroxisome proliferator-activated receptors pathways - Jia-Da Zhang; Sen He; Ting-Ting He; Chuan-Hai Li; Bing-Hua Yan; Yuan Yang; Jian Yang; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Environmental Pollution, 2024)

Elimination method of sliding blockage effect in discrete element simulation of rolling stone based on discrete fracture network and damping joint model - You Zhou; Huai-Zhong Liu; Hong-Qiang Xie; Li Zhuo; Ming-Li Xiao; Jiang-Da He; Jian-Liang Pei; Guo-Wen Xu (Computers and Geotechnics, 2024)

Coupling urchin-like TiO2 nanospheres with nitrogen and sulfur co-doped graphene quantum dots for visible-light-induced degradation of toluene - Juntao Tang; Jiaxin Zhu; Luzhen Liu; Lin Xia; Zhiqiao He; Da Wang; Xing Xu; Shuang Song (Chemical Engineering Journal, 2024)

Inhibition of nucleotide metabolism with dual-template epitope imprinted nanoparticles for targeted HER2+ tumor therapy - Xing-Hui Ren; Lei Shi; Zi-Bo Ma; Da-Wei Wang; Xi-Wen He; Wen-You Li; Yu-Kui Zhang (Chemical Engineering Journal, 2024)

Mechanism of enhanced microalgal biomass and lipid accumulation through symbiosis between a highly succinic acid-producing strain of Escherichia coli SUC and Aurantiochytrium sp. SW1 - Mei-Yu Zhang; Xin-Ru Xu; Ru-Ping Zhao; Chao Huang; Yuan-Da Song; Zi-Tong Zhao; Yu-Bin Zhao; Xiao-Jie Ren; Xin-He Zhao (Bioresource Technology, 2024)

A unique subseafloor microbiosphere in the Mariana Trench driven by episodic sedimentation - Jiwen Liu; Da-Wei Li; Xinxin He; Ronghua Liu; Haojin Cheng; Chenglong Su; Mengna Chen; Yonghong Wang; Zhongsheng Zhao; Hanyue Xu; Zhangyu Cheng; Zicheng Wang; et al. (Marine Life Science & Technology, 2024)
Hadal trenches are characterized by enhanced and infrequent high-rate episodic sedimentation events that likely introduce not only labile organic carbon and key nutrients but also new microbes that significantly alter the subseafloor microbiosphere. Currently, the role of high-rate episodic sedimentation in controlling the composition of the hadal subseafloor microbiosphere is unknown. Here, analyses of carbon isotope composition in a ~ 750 cm long sediment core from the Challenger Deep revealed noncontinuous deposition, with anomalous 14 C ages likely caused by seismically driven mass transport and the funneling effect of trench geomorphology. Microbial community composition and diverse enzyme activities in the upper ~ 27 cm differed from those at lower depths, probably due to sudden sediment deposition and differences in redox condition and organic matter availability. At lower depths, microbial population numbers, and composition remained relatively constant, except at some discrete depths with altered enzyme activity and microbial phyla abundance, possibly due to additional sudden sedimentation events of different magnitude. Evidence is provided of a unique role for high-rate episodic sedimentation events in controlling the subsurface microbiosphere in Earth’s deepest ocean floor and highlight the need to perform thorough analysis over a large depth range to characterize hadal benthic populations. Such depositional processes are likely crucial in shaping deep-water geochemical environments and thereby the deep subseafloor biosphere.

Correction to: Characterization of YABBY genes in Dendrobium officinale reveals their potential roles in flower development - Danqi Zeng; Can Si; Jaime A. Teixeira da Silva; Guangyi Dai; Jun Duan; Chunmei He (Protoplasma, 2024)

Constructed electron-dense Mn sites in nitrogen-doped Mn3O4 for efficient catalytic ozonation of pyrazines: Degradation and odor elimination - Yinning He; Jiayi Li; Jingyu Tang; Haijun Cheng; Tao Zeng; Zhiqiao He; Da Wang; Lizhang Wang; Shuang Song; Jun Ma (Water Research, 2023)

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

Very fine spatial resolution urban land cover mapping using an explicable sub-pixel mapping network based on learnable spatial correlation - Da He; Qian Shi; Jingqian Xue; Peter M. Atkinson; Xiaoping Liu (Remote Sensing of Environment, 2023)

Hydrophobic fluorine-doped carbon-wrapped TiO2 particles as efficient and stable photocatalysts for gaseous toluene degradation - Lei Lai; Juntao Tang; Jiaxin Zhu; Da Wang; Zhiqiao He; Shuang Song (Journal of Environmental Chemical Engineering, 2023)

Analysis of research status and trends on marine benthic dinoflagellate toxins: A bibliometric study based on web of science database and VOSviewer - Jing-Qian Tang; Qian-Hui Shen; Yao-Yao Han; Yang Wu; Xiang-Feng He; Da-Wei Li; Yong Huang (Environmental Research, 2023)

Widespread clay authigenesis and highly congruent silicate weathering in the Marinoan aftermath - Yi-Sheng Yin; Guang-Yi Wei; Philip A.E. Pogge von Strandmann; Maxwell A. Lechte; Simon V. Hohl; Yi-Bo Lin; Da Li; Tianyu Chen; Tao Yang; Feifei Zhang; Terry T. Isson; He Zhang; et al. (Earth and Planetary Science Letters, 2023)

Effect of rGO content on enhanced Photo-Fenton degradation of Venlafaxine using rGO encapsulated magnetic hexagonal FeTiO3 nanosheets - Da Wang; Stefanos Giannakis; Jingyu Tang; Kai Luo; Juntao Tang; Zhiqiao He; Shuang Song; Lizhang Wang (Chemical Engineering Journal, 2023)

Understanding the promotion mechanism of boron during the surface reconstruction of Ni2B nanoflakes for efficient urea electrocatalytic oxidation - Jiadian Chen; Huayu Chen; Hang Yin; He He; Zehao Wang; Dandan Yu; Junhui Liang; Yuexiang Huang; Laishun Qin; Da Chen (Chemical Engineering Journal, 2023)

Salviamilthone A-O, diterpenoid quinones from Salvia miltiorrhiza - Ying-Jie Ren; Yan-Gang Cao; Meng-Nan Zeng; Qin-Qin Zhang; Yan-Ling Liu; Chen He; Xu Chen; Xi-Ling Fan; Xiang-Da Li; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry, 2023)

Boosting photocatalytic H2 evolution on UIO-66-NH2/covalent triazine–based frameworks composites by constructing a covalent heterojunction - Shiwen Dong; Xuan Liu; Xianxian Kong; Feilong Dong; Yan Yu; Lizhang Wang; Da Wang; Zhiqiao He; Shuang Song (Environmental Science and Pollution Research, 2023)

In situ microwave-assisted preparation of NS-codoped carbon dots stabilized silver nanoparticles as an off-on fluorescent probe for trace Hg2+ detection - Pengyuan Yin; Tianru Zou; Guixiang Yao; Shaoqing Li; Yanzhi He; Guizhen Li; Da Li; Wei Tan; Min Yang (Chemosphere, 2023)

The role of ubiquitous metal ions in degradation of microplastics in hot-compressed water - Tan-Phat Vo; Jukka Rintala; Leilei Dai; Wen-Da Oh; Chao He (Water Research, 2023)

Atomically dispersed vanadium on g-C3N4 for effective ciprofloxacin degradation via peroxymonosulfate activation: Insights on the nonradical pathway and V redox cycles - Mohamed Faisal Gasim; Siew-Chun Low; Chao He; Kun-Yi Andrew Lin; Tuan Sherwyn Hamidon; M. Hazwan Hussin; Wen-Da Oh (Journal of Environmental Chemical Engineering, 2023)

Sustainable utilization of Sedum plumbizincicola as superior hydrochar for efficient nutrients recovery - Ruichi Zhang; Yizhong Zhang; Ronn Goei; Wen-Da Oh; Zhao Zhang; Chao He (Journal of Environmental Management, 2023)

Multiple Palaeozoic–Mesozoic orogenic events in the SE Yangtze Block, China: evidence from the petrogenesis and deformation of gneissic granites from the Nanwenhe metamorphic dome and regional correlation analysis - Xinming Zhang; Da Zhang; Jinbo Pan; Minfeng Bi; Ganguo Wu; Xiaolong He; Bojie Hu; Chaoyang Que; Yongjun Di; Wei Xue (International Geology Review, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Loss of OsARF18 function confers glufosinate resistance in rice - Jin-Qiu Xia; Da-Yu He; Qin-Yu Liang; Zheng-Yi Zhang; Jie Wu; Zi-Sheng Zhang; Jing Zhang; Lin Wang; Cong-He Zhang; Ping-Xia Zhao; Cheng-Bin Xiang (Molecular Plant, 2023)

Improving the performance of incineration fly ash as cement admixture by high-temperature sintering and its toxic leaching characteristics - Xiaodong Ma; Tingshu He; Yongqi Da; Yongdong Xu; Fengwa Zhao; Yuhao Sun; Renhe Yang (Journal of Cleaner Production, 2023)

Experiment study on reactive powder concrete beams using spirals reinforcement under torsion - Xia Cao; Yong-peng Quan; Yi-cheng Ren; Feng Fu; Qi-zhi Jin; Da-bo He; Yan Zheng (Engineering Structures, 2023)

Valorization of soybean plant wastes in preparation of N-doped biochar for catalytic ozonation of organic contaminants: Atrazine degradation performance and mechanistic considerations - Shiwen Dong; Xing Shen; Qingqing Guo; Haijun Cheng; Stefanos Giannakis; Zhiqiao He; Lizhang Wang; Da Wang; Shuang Song; Jun Ma (Chemical Engineering Journal, 2023)

Rice Straw Biochar is More Beneficial to Soil Organic Carbon Accumulation and Stabilization than Rice Straw and Rice Straw Ash - Mengru He; Ya Jiang; Yuhang Han; Wenhao Zhu; Da Meng; Cuilan Li; Hongguang Cai; Jinjing Zhang (Journal of Soil Science and Plant Nutrition, 2023)

Impact of host plants on biological characteristics and Vg/VgR expression of Spodoptera frugiperda - Shi-Peng Han; Ya-Yuan Zhou; Da Wang; Qiu-Ju Qin; Peng Song; Yun-Zhuan He (Journal of Pest Science, 2023)

Correction to: Genome‑wide characterization of long terminal repeat retrotransposons provides insights into trait evolution of four cucurbit species - Hai‑Nan Liu; Mao‑Song Pei; Charles Ampomah‑Dwamena; Guang‑Qi He; Tong‑Lu Wei; Qiao‑Fang Shi; Yi‑He Yu; Da‑Long Guo (Functional & Integrative Genomics, 2023)

Genome-wide characterization of long terminal repeat retrotransposons provides insights into trait evolution of four cucurbit species - Hai-Nan Liu; Mao-Song Pei; Charles Ampomah-Dwamena; Guang-Qi He; Tong-Lu Wei; Qiao-Fang Shi; Yi-He Yu; Da-Long Guo (Functional & Integrative Genomics, 2023)

High quality diet attenuated the positive association between polychlorinated biphenyls and premature mortality among middle-aged and older adults - Weigui Ni; Qingping Xue; Shanshan Zhang; Xue Yang; Shiyi Wu; Xingchen He; Yan Xiao; Wenling Chang; Ying Wen; Yichao Huang; Yi-Xin Wang; Da Chen; et al. (Environmental Research, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Physical properties, chemical composition, and toxicity leaching of incineration fly ash by multistage water washing - Xiaodong Ma; Tingshu He; Yongqi Da; Yongdong Xu; Zhenmin Wan (Environmental Science and Pollution Research, 2023)

Potential influence of nutrients intake by adults on the population dynamics of Athetis lepigone (Lepidoptera: Noctuidae) - Yayuan Zhou; Peng Song; Dan Luo; Zhaoyang Feng; Da Wang; Yunzhuan He (Journal of Asia-Pacific Entomology, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

Screening of organophosphate esters in different indoor environments: Distribution, diffusion, and risk assessment - Tianqi Jia; Lirong Gao; Wenbin Liu; Bobo Guo; Yunchen He; Xiaotian Xu; Tianao Mao; Jinglin Deng; Da Li; Fang Tao; Wenwen Wang (Environmental Pollution, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Combined methods elucidate the multi-organ toxicity of cylindrospermopsin (CYN) on Daphnia magna - Zhongshi He; Youxin Chen; Da Huo; Jin Gao; Yewei Xu; Rui Yang; Yiming Yang; Gongliang Yu (Environmental Pollution, 2023)

Efficient degradation of 2,3,5-trimethylpyrazine by catalytic ozonation over MnOx supported on biochar derived from waste tea leaves - Yinning He; Yi Chen; Jinzhe Li; Da Wang; Shuang Song; Feilong Dong; Zhiqiao He (Chemical Engineering Journal, 2023)

A simple and efficient protocol for transient transformation of sliced grape berries - Mao-Song Pei; Hai-Nan Liu; Charles Ampomah-Dwamena; Tong-Lu Wei; Yi-He Yu; Jia-Bing Jiao; Ying-Ying Lv; Feng Li; Hong-Chao Li; Xue-Jie Zhu; Da-Long Guo (Protoplasma, 2023)

Hollow urchin-shaped NCM811 ternary-structure for high rate charge/discharge capability and efficient CO2 adsorption - Fan-Ming Yang; Xiao-Yao Zhou; Xi-Da Li; Zhi-Cheng Yi; Rong Feng; Guo-Wen He (Journal of Environmental Chemical Engineering, 2023)

Functional Autapses Form in Striatal Parvalbumin Interneurons but not Medium Spiny Projection Neurons - Xuan Wang; Zhenfeng Shu; Quansheng He; Xiaowen Zhang; Luozheng Li; Xiaoxue Zhang; Liang Li; Yujie Xiao; Bo Peng; Feifan Guo; Da-Hui Wang; Yousheng Shu (Neuroscience Bulletin, 2023)

Modeling human gray hair by irradiation as a valuable tool to study aspects of tissue aging - Da-mao Dai; Ye He; Qing Guan; Zhe-xiang Fan; Yunmin Zhu; Jin Wang; Shulian Wu; Jian Chen; Demengjie Le; Zhi-qi Hu; Qian Qu; Yong Miao (GeroScience, 2023)

Effect of metal doping (Me = Zn, Cu, Co, Mn) on the performance of bismuth ferrite as peroxymonosulfate activator for ciprofloxacin removal - Pooi-Ling Koo; Zheng-Yi Choong; Chao He; Yueping Bao; Nur Farhana Jaafar; Wen-Da Oh (Chemosphere, 2023)

Impacts of global urban expansion on natural habitats undermine the 2050 vision for biodiversity - Qiang Ren; Chunyang He; Qingxu Huang; Da Zhang; Peijun Shi; Wenlu Lu (Resources, Conservation and Recycling, 2023)

Folic acid delays postharvest quality deterioration of table grape by regulating cell wall metabolism-associated hub WRKY31 transcription factor - Mao-Song Pei; Hai-Nan Liu; Yi-He Yu; Tong-Lu Wei; Da-Long Guo (Postharvest Biology and Technology, 2023)

Insight into the mechanism of gasification fine slag enhanced flotation with selective dispersion flocculation - Da Shi; Jianbo Zhang; Huiquan Li; Shaopeng Li; Fayu He; Jiangshan Qu; Ruiqi Chang; Ganyu Zhu; Chennian Yang; Chenye Wang (Fuel, 2023)

Development of an automated solid phase extraction instrument for determination of lead in high-salt foods - Yabing Xiao; Yihan He; Chao Ji; Marti Z. Hua; Wei Liu; Shuang Yang; Da Chen; Wenjie Zheng; Xiaonan Lu (Food Chemistry, 2023)

Characterization of YABBY genes in Dendrobium officinale reveals their potential roles in flower development - Danqi Zeng; Can Si; Jaime A. Teixeira da Silva; Guangyi Dai; Juan Duan; Chunmei He (Protoplasma, 2023)

Electron transfer enhancing the Mn(II)/Mn(III) cycle in MnO/CN towards catalytic ozonation of atrazine via a synergistic effect between MnO and CN - Da Wang; Yinning He; Yi Chen; Fan Yang; Zhiqiao He; Tao Zeng; Xiaohui Lu; Lizhang Wang; Shuang Song; Jun Ma (Water Research, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

A novel protein domain is important for photosystem II complex assembly and photoautotrophic growth in angiosperms - Wei Li; Jiangfan Guo; Xue Han; Xiaowen Da; Kai Wang; Hongfei Zhao; Shi-Tang Huang; Bosheng Li; Hang He; Ruirui Jiang; Shichen Zhou; Peng Yan; et al. (Molecular Plant, 2023)

Single-kernel classification of deoxynivalenol and zearalenone contaminated maize based on visible light imaging under ultraviolet light excitation combined with polarized light imaging - Maozhen Qu; Shijie Tian; Hengjie Yu; Da Liu; Chao Zhang; Yingchao He; Fang Cheng (Food Control, 2023)

Cognitive changes are associated with increased blood-brain barrier leakage in non-brain metastases lung cancer patients - Da-Fu Zhang; Zhen-Hui Li; Zhi-Ping Zhang; Yin-Fu He; Bin-Li Shang; Xiu-Feng Xu; Ying-Ying Ding; Yu-Qi Cheng (Brain Imaging and Behavior, 2023)
To explore the relationship between cognitive function and blood–brain barrier leakage in non-brain metastasis lung cancer and healthy controls. 75 lung cancers without brain metastasis and 29 healthy controls matched with age, sex, and education were evaluated by cognitive assessment, and the Patlak pharmacokinetic model was used to calculate the average leakage in each brain region according to the automated anatomical labeling atlas. After that, the relationships between cognitive and blood–brain barrier leakage were evaluated. Compared with healthy controls, the leakage of bilateral temporal gyrus and whole brain gyrus were higher in patients with lung cancers ( P < 0.05), mainly in patients with advanced lung cancer ( P < 0.05), but not in patients with early lung cancer ( P > 0.05). The cognitive impairment of advanced lung cancers was mainly reflected in the damage of visuospatial/executive, and delayed recall. The left temporal gyrus with increased blood–brain barrier leakage showed negative correlations with delayed recall (r = -0.201, P = 0.042). An increase in blood–brain barrier leakage was found in non-brain metastases advanced lung cancers that corresponded to decreased delayed recall. With progression in lung cancer staging, blood–brain barrier shows higher leakage and may lead to brain metastases and lower cognitive development.

Catalytic ozonation of atrazine with stable boron-doped graphene nanoparticles derived from waste polyvinyl alcohol film: Performance and mechanism - Da Wang; Shiwen Dong; Hangkai Hu; Zhiqiao He; Feilong Dong; Juntao Tang; Xiaohui Lu; Lizhang Wang; Shuang Song; Jun Ma (Chemical Engineering Journal, 2023)

Correction to: Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2023)

Effects of the Dicranopteris linearis root system and initial moisture content on the soil disintegration characteristics of gully erosion - Ling He; Yu-song Deng; Qiu-yue Tang; Da-lan Liao; Chao Wang; Xiao-qian Duan (Journal of Mountain Science, 2022)

The impacts of probiotics in eradication therapy of Helicobacter pylori - Xiaofen Bai; Minjie Zhu; Yajun He; Tengyan Wang; Da Tian; Jianchang Shu (Archives of Microbiology, 2022)
Helicobacter pylori ( H. pylori ) is a well-known pathogen that infects approximately half of the world’s population. It is a pathogenic agent with potential health hazards related to diverse diseases, especially digestive diseases, such as chronic gastritis, peptic ulcer, and gastric carcinoma. In clinical, antibiotics are commonly applied in eradication therapy of H. pylori . However, the increase in antibiotic resistance and side effects has induced the failure of eradication therapy. Recent studies have shown that probiotic supplementation has promising application prospects. It can restore the gastrointestinal microbiota balance and prevent dysbacteriosis caused by antibiotics. Furthermore, it has been reported to have direct or indirect inhibitory effects on H. pylori . Probiotics may have a beneficial effect on H. pylori eradication. However, the strain, dosages, duration times, and safety of probiotic supplementation need further study before clinical applications.

Germanium enrichment in sphalerite with acicular and euhedral textures: an example from the Zhulingou carbonate-hosted Zn(-Ge) deposit, South China - Kai Luo; Alexandre Cugerone; Mei-Fu Zhou; Jia-Xi Zhou; Guo-Tao Sun; Jing Xu; Kang-Jian He; Mao-Da Lu (Mineralium Deposita, 2022)

Long‐term drought aggravates instability of alpine grassland productivity to extreme climatic event - Yun L. He; Jin S. Wang; Da S. Tian; Quan Quan; Lin Jiang; Fang F. Ma; Lu Yang; Fang Y. Zhang; Qing P. Zhou; Shu L. Niu (Ecology, 2022)
The frequency and severity of extreme weather events are increasing and expected to increase more in the future, together with global change. However, how extreme events and global change factors interactively influence community structures and ecosystem processes is largely unknown. Here, we investigated the responses of the temporal stability and resilience of aboveground net primary productivity (ANPP) of an alpine meadow to an extreme flooding event under different treatments of experimental drought and clipping. We found that ecosystems that were exposed to drought treatments for 3 years significantly decreased the temporal stability of community productivity but increased resilience to flooding, whereas their resistance to or recovery from flooding did not change. Neither clipping nor its interaction with drought altered the responses of these community stability metrics to flooding. Drought treatments significantly decreased plant species richness and asynchrony and dominant species stability, leading to a decrease in temporal stability and an increase in resilience in response to the extreme flooding event. The study also revealed that the change in species asynchrony was the dominant impact pathway determining the responses of resilience and temporal stability to flooding. Our results highlight that alpine grassland that experiences a multiyear drought may aggravate the instability of community productivity to extreme climatic events by reducing species asynchrony.

Genome-wide identification and expression analysis of JmjC domain–containing genes in grape under MTA treatment - Yi-Zhe Cheng; Guang-Qi He; Sheng-Di Yang; Shuai-Hui Ma; Jin-Ping Ma; Fang-Hui-Zi Shang; Xu-Fei Li; Hui-Ying Jin; Da-Long Guo (Functional & Integrative Genomics, 2022)

Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2022)

Piperock ichnofabrics from western Henan, China: spatial distribution pattern and environmental controls on middle Cambrian carbonates - Bingchen Liu; Da Li; Min Wang; Mingyue Dai; Wenyi He; Jingbo Li; Yong’an Qi (International Journal of Earth Sciences, 2022)

Distance decay 2.0 – A global synthesis of taxonomic and functional turnover in ecological communities - Caio Graco‐Roza; Sonja Aarnio; Nerea Abrego; Alicia T. R. Acosta; Janne Alahuhta; Jan Altman; Claudia Angiolini; Jukka Aroviita; Fabio Attorre; Lars Baastrup‐Spohr; José J. Barrera‐Alba; Jonathan Belmaker; et al. (Global Ecology and Biogeography, 2022)
Aim Understanding the variation in community composition and species abundances (i.e., β‐diversity) is at the heart of community ecology. A common approach to examine β‐diversity is to evaluate directional variation in community composition by measuring the decay in the similarity among pairs of communities along spatial or environmental distance. We provide the first global synthesis of taxonomic and functional distance decay along spatial and environmental distance by analysing 148 datasets comprising different types of organisms and environments. Location Global. Time period 1990 to present. Major taxa studied From diatoms to mammals. Method We measured the strength of the decay using ranked Mantel tests (Mantel r ) and the rate of distance decay as the slope of an exponential fit using generalized linear models. We used null models to test whether functional similarity decays faster or slower than expected given the taxonomic decay along the spatial and environmental distance. We also unveiled the factors driving the rate of decay across the datasets, including latitude, spatial extent, realm and organismal features. Results Taxonomic distance decay was stronger than functional distance decay along both spatial and environmental distance. Functional distance decay was random given the taxonomic distance decay. The rate of taxonomic and functional spatial distance decay was fastest in the datasets from mid‐latitudes. Overall, datasets covering larger spatial extents showed a lower rate of decay along spatial distance but a higher rate of decay along environmental distance. Marine ecosystems had the slowest rate of decay along environmental distances. Main conclusions In general, taxonomic distance decay is a useful tool for biogeographical research because it reflects dispersal‐related factors in addition to species responses to climatic and environmental variables. Moreover, functional distance decay might be a cost‐effective option for investigating community changes in heterogeneous environments.

Metabolic accumulation and related synthetic genes of O-acetyl groups in mannan polysaccharides of Dendrobium officinale - Can Si; Chunmei He; Jaime A. Teixeira da Silva; Zhenming Yu; Jun Duan (Protoplasma, 2022)

Metabolic tuning of a stable microbial community in the surface oligotrophic Indian Ocean revealed by integrated meta-omics - Zhang-Xian Xie; Ke-Qiang Yan; Ling-Fen Kong; Ying-Bao Gai; Tao Jin; Yan-Bin He; Ya-Yu Wang; Feng Chen; Lin Lin; Zhi-Long Lin; Hong-Kai Xu; Zong-Ze Shao; et al. (Marine Life Science & Technology, 2022)
Understanding the mechanisms, structuring microbial communities in oligotrophic ocean surface waters remains a major ecological endeavor. Functional redundancy and metabolic tuning are two mechanisms that have been proposed to shape microbial response to environmental forcing. However, little is known about their roles in the oligotrophic surface ocean due to less integrative characterization of community taxonomy and function. Here, we applied an integrated meta-omics-based approach, from genes to proteins, to investigate the microbial community of the oligotrophic northern Indian Ocean. Insignificant spatial variabilities of both genomic and proteomic compositions indicated a stable microbial community that was dominated by Prochlorococcus , Synechococcus , and SAR11. However, fine tuning of some metabolic functions that are mainly driven by salinity and temperature was observed. Intriguingly, a tuning divergence occurred between metabolic potential and activity in response to different environmental perturbations. Our results indicate that metabolic tuning is an important mechanism for sustaining the stability of microbial communities in oligotrophic oceans. In addition, integrated meta-omics provides a powerful tool to comprehensively understand microbial behavior and function in the ocean.

Root-associated microbiota drive phytoremediation strategies to lead of Sonchus Asper (L.) Hill as revealed by intercropping-induced modifications of the rhizosphere microbiome - Xinyue Mei; Ying Wang; Zuran Li; Marie Larousse; Arthur Pere; Martine da Rocha; Fangdong Zhan; Yongmei He; Linlong Pu; Franck Panabières; Yanqun Zu (Environmental Science and Pollution Research, 2022)
Intercropping or assistant endophytes promote phytoremediation capacities of hyperaccumulators and enhance their tolerance to heavy metal (HM) stress. Findings from a previous study showed that intercropping the hyperaccumulator Sonchus asper (L.) Hill grown in HM-contaminated soils with maize improved the remediating properties and indicated an excluder-to-hyperaccumulator switched mode of action towards lead. In the current study, RNA-Seq analysis was conducted on Sonchus roots grown under intercropping or monoculture systems to explore the molecular events underlying this shift in lead sequestering strategy. The findings showed that intercropping only slightly affects S. asper transcriptome but significantly affects expression of root-associated microbial genomes. Further, intercropping triggers significant reshaping of endophytic communities associated with a ‘root-to-shoot’ transition of lead sequestration and improved phytoremediation capacities of S. asper . These findings indicate that accumulator activities of a weed are partially attributed to the root-associated microbiota, and a complex network of plant–microbe-plant interactions shapes the phytoremediation potential of S. asper . Analysis showed that intercropping may significantly change the structure of root-associated communities resulting in novel remediation properties, thus providing a basis for improving phytoremediation practices to restore contaminated soils.

Mitogenome of Knodus borki (Cypriniformes: Characidae): genomic characterization and phylogenetic analysis - Cheng-He Sun; Ya-Nan Zhang; Xiao-Shu Zeng; Da-Wei Liu; Qi Huang; Xiao-Li Zhang; Qun Zhang (Molecular Biology Reports, 2022)

Identification and expression analysis of grape LRK10L-2 genes during grape fruit development - Jin-Ping Ma; Xue-Ren Yin; Tong-Lu Wei; Hai-Nan Liu; Mao-Song Pei; Sheng-Di Yang; Hui-Ying Jin; Guang-Qi He; Da-Long Guo (Plant Biotechnology Reports, 2022)

HMGB1-RAGE Pathway Contributes to the Abnormal Migration of Endogenous Subventricular Zone Neural Progenitors in an Experimental Model of Focal Microgyria - Yi-Wen Mei; Tian-Lan Huang; Xin Chen; Si-Xun Yu; Jie Li; Zhi Zhang; Yang He; Da-qing Guo; Hai-Feng Shu (Journal of Molecular Neuroscience, 2022)

Comparing soil-to-plant cadmium (Cd) transfer and potential human intake among rice cultivars with different Cd tolerance levels grown in a tropical contaminated soil - Thiago Assis Rodrigues Nogueira; Takashi Muraoka; Laís Karina Silveira; Jamile Santos da Silva; Cassio Hamilton Abreu-Junior; José Lavres; Adriana Pinheiro Martinelli; Marcelo Carvalho Minhoto Teixeira Filho; Zhenli He; Arun Dilipkumar Jani; Antonio Ganga; Gian Franco Capra (Environmental Monitoring and Assessment, 2022)

Purple non-sulfur bacteria technology: a promising and potential approach for wastewater treatment and bioresources recovery - Haifeng Lu; Guangming Zhang; Shichao He; Ruihan Zhao; Da Zhu (World Journal of Microbiology and Biotechnology, 2021)

Ectopic expression of DoFLS1 from Dendrobium officinale enhances flavonol accumulation and abiotic stress tolerance in Arabidopsis thaliana - Zhenming Yu; Wei Dong; Jaime A. Teixeira da Silva; Chunmei He; Can Si; Jun Duan (Protoplasma, 2021)

Investigation on Hydrodynamic Performance of Flapping Foil Interacting with Oncoming Von Kármán Wake of a D-Section Cylinder - Jian Li; Peng Wang; Xiaoyi An; Da Lyu; Ruixuan He; Baoshou Zhang (Journal of Marine Science and Engineering, 2021)
Flapping foils are studied to achieve an efficient propeller. The performance of the flapping foil is influenced by many factors such as oncoming vortices, heaving amplitude, and geometrical parameters. In this paper, investigations are performed on flapping foils to assess its performance in the wake of a D-section cylinder located half a diameter in front of the foil. The effects of heaving amplitude and foil thickness are examined. The results indicate that oncoming vortices facilitate the flapping motion. Although the thrust increases with the increasing heaving amplitude, the propelling efficiency decreases with it. Moreover, increasing thickness results in higher efficiency. The highest propelling efficiency is achieved when the heaving amplitude equals ten percent of the chord length with a symmetric foil type of NACA0050 foil. When the heaving amplitude is small, the influence of the thickness tends to be more remarkable. The propelling efficiency exceeds 100% and the heaving amplitude is 10% of the chord length when the commonly used equation is adopted. This result demonstrates that the flapping motion extracts some energy from the oncoming vortices. Based on the numerical results, a new parameter, the energy transforming ratio (RET), is applied to explicate the energy transforming procedure. The RET represents that the flapping foil is driven by the engine or both the engines and the oncoming vortices with the range of RET being (0, Infini) and (−1, 0), respectively. With what has been discussed in this paper, the oncoming wake of the D-section cylinder benefits the flapping motion which indicates that the macro underwater vehicle performs better following a bluff body.

Stoichiometric relations of C, N, and P in urban top soils in Nanjing, China, and their biogeochemical implications - Jin-Ling Yang; Da-Gang Yuan; Yu-Guo Zhao; Yue He; Gan-Lin Zhang (Journal of Soils and Sediments, 2021)

Endoplasmic Reticulum Stress Regulates Cardiomyocyte Apoptosis in Myocardial Fibrosis Development via PERK-Mediated Autophagy - Changjiang Zhang; Yuanhong Li; Jingbo Zhao; Ke Su; Ke He; Yurong Da; Hao Xia (Cardiovascular Toxicology, 2020)

Transcriptome sequencing and metabolite profiling analyses provide comprehensive insight into molecular mechanisms of flower development in Dendrobium officinale (Orchidaceae) - Chunmei He; Xuncheng Liu; Jaime A. Teixeira da Silva; Nan Liu; Mingze Zhang; Jun Duan (Plant Molecular Biology, 2020)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Effect of Chinese Rice Wine on the Endogenous Protease Activity, Myofibrillar Degradation, and Quality Characteristics in Topmouth Culter ( Culter alburnus ) - Fan Wang; Jia-Liang He; Tursunay Turgun; Da-E Ge; Nurgul Rahman; Jian-Zhong Zhou; Xiao-Li Liu (Journal of Aquatic Food Product Technology, 2020)

Experimental study on the dynamic properties of lime-solidified soft soil under cyclic loading - Guijie Zhao; Huan Yan; Ying Yan; Shaobo Gao; Da Fan; Yang He; Yu Wang (Arabian Journal of Geosciences, 2020)

Enhanced long-term attenuation of 1,4-dioxane in bioaugmented flow-through aquifer columns - Marcio Luis Busi da Silva; Ya He; Jacques Mathieu; Pedro J. J. Alvarez (Biodegradation, 2020)

Three new ɑ-pyrone derivatives induced by chemical epigenetic manipulation of Penicillium herquei , an endophytic fungus isolated from Cordyceps sinensis - Da-Le Guo; Ling Qiu; Dan Feng; Xin He; Xiao-Hua Li; Zhi-Xing Cao; Yu-Cheng Gu; Ling Mei; Fang Deng; Yun Deng (Natural Product Research, 2020)

Effects of Organic Copper on Growth Performance and Oxidative Stress in Mice - Mingyu Zhi; Ping Tang; Ying Liu; Da He; Suxia Zheng (Biological Trace Element Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Protective role of curcumin in cadmium-induced testicular injury in mice by attenuating oxidative stress via Nrf2/ARE pathway - Shu-Hua Yang; Jian-Bin He; Li-Hui Yu; Lin Li; Miao Long; Ming-Da Liu; Peng Li (Environmental Science and Pollution Research, 2019)

Methodology for production logging in oil-in-water flows under low flow rate and high water-cut conditions - Da-Yang Wang; Ning-De Jin; Lu-Sheng Zhai; Ying-Yu Ren; Yuan-Sheng He (Applied Geophysics, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

Applications of Raman spectroscopic techniques for quality and safety evaluation of milk: A review of recent developments - Huirong He; Da-Wen Sun; Hongbin Pu; Lijun Chen; Li Lin (Critical Reviews in Food Science and Nutrition, 2019)

The Contributions of Climate Changes and Human Activities to Long-Term Variations in Lake Sediments Based on Results from Generalized Additive Models - Zhuoshi He; Shouliang Huo; Chunzi Ma; Hanxiao Zhang; Da An; Beidou Xi; Qiujing Xu; Xinghui Xia; Fengchang Wu (Water Resources Management, 2019)

Trophic Interaction in a Portunus rituberculatus Polyculture Ecosystem Based on Carbon and Nitrogen Stable Isotope Analysis - Jie Feng; Xiangli Tian; Shuanglin Dong; Da Li; Ruipeng He; Kai Zhang; Dongxu Zhang; Qingqi Zhang (Journal of Ocean University of China, 2018)

Investigating the composition characteristics of dissolved and particulate/colloidal organic matter in effluent-dominated stream using fluorescence spectroscopy combined with multivariable analysis - Min-Da Yu; Xiao-Song He; Bei-Dou Xi; Ru-Tai Gao; Xian-Wei Zhao; Hui Zhang; Cai-Hong Huang; Wenbing Tan (Environmental Science and Pollution Research, 2018)

Notch ligand Delta-like1 enhances degranulation and cytokine production through a novel Notch/Dok-1/MAPKs pathway in vitro - Songsong Jiang; Yifan Da; Shiwen Han; Yahong He; Huilian Che (Immunologic Research, 2018)

Molecular cloning and functional analysis of DoUGE related to water-soluble polysaccharides from Dendrobium officinale with enhanced abiotic stress tolerance - Zhenming Yu; Chunmei He; Jaime A. Teixeira da Silva; Guihua Zhang; Wei Dong; Jianping Luo; Jun Duan (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Occurrence and risk assessment of phthalate esters (PAEs) in agricultural soils of the Sanjiang Plain, northeast China - He Wang; Hong Liang; Da-Wen Gao (Environmental Science and Pollution Research, 2017)

Molecular cloning and functional analysis of the phosphomannomutase (PMM) gene from Dendrobium officinale and evidence for the involvement of an abiotic stress response during germination - Chunmei He; Songjun Zeng; Jaime A. Teixeira da Silva; Zhenming Yu; Jianwen Tan; Jun Duan (Protoplasma, 2017)

Non-Destructive and rapid evaluation of staple foods quality by using spectroscopic techniques: A review - Wen-Hao Su; Hong-Ju He; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2017)

Glucocorticoids Prevent Enterovirus 71 Capsid Protein VP1 Induced Calreticulin Surface Exposure by Alleviating Neuronal ER Stress - Dan-Dan Hu; Jian-Ning Mai; Li-Ya He; Pei-Qing Li; Wen-Xiong Chen; Jian-Jiang Yan; Wei-Dong Zhu; Li Deng; Dan Wei; Di-Hui Liu; Si-Da Yang; Zhi-Bin Yao (Neurotoxicity Research, 2017)

Variations and trends of trans-boundary runoff in the longitudinal range-gorge region - Yan-ling Yu; Feng Pan; Xin-you Liu; Wen-hua Chen; Da-ming He (Journal of Mountain Science, 2017)

New isocoumarin and stilbenoid derivatives from the tubers of Sparganium stoloniferum (Buch.-Ham.) - Da-Wei Wu; Qiao-Li Liang; Xiao-Long Zhang; Zheng Jiang; Xiu-He Fan; Wei Yue; Qi-Nan Wu (Natural Product Research, 2017)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

3D seismic interpretation of subsurface eruptive centers in a Permian large igneous province, Tazhong Uplift, central Tarim Basin, NW China - Jiangfeng Yang; Wenbin Zhu; Da Guan; Beibei Zhu; Liansheng Yuan; Xuemei Xiang; Jinbao Su; Jingwen He; Xinhui Wu (International Journal of Earth Sciences, 2016)

Ag/Ag2SO3 plasmonic catalysts with high activity and stability for CO2 reduction with water vapor under visible light - Da Wang; Yan Yu; Zhipeng Zhang; Huiying Fang; Jianmeng Chen; Zhiqiao He; Shuang Song (Environmental Science and Pollution Research, 2016)

Spatial and temporal variation of drought index in a typical steep alpine terrain in Hengduan Mountains - Gno-feng Zhu; Ling Yang; Da-he Qin; Hua-li Tong; Yuan-feng Liu; Jia-fang Li (Journal of Mountain Science, 2016)

A new triterpenoid saponin from Clinopodium chinense (Benth.) O. Kuntze - Biao Zeng; Guang-Da Liu; Bao-Bao Zhang; Shan-shan Wang; Rui Ma; Bei-Shan Zhong; Bai-qiu He; Yan Liang; Fei-Hua Wu (Natural Product Research, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Impacts of snow disaster on meat production and adaptation: an empirical analysis in the yellow river source region - Yi-ping Fang; Chen Zhao; Yong-jian Ding; Da-he Qin; Jia-li Huang (Sustainability Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

Photoinactivation of Photosystem II in wild-type and chlorophyll b-less barley leaves: which mechanism dominates depends on experimental circumstances - Jie He; Wenquan Yang; Lin Qin; Da-Yong Fan; Wah Soon Chow (Photosynthesis Research, 2015)

Molecular mapping and markers for leaf rust resistance gene Lr24 in CIMMYT wheat line 19HRWSN-122 - Ai-yong Qi; Pei-pei Zhang; Xian-chun Xia; Zhong-hu He; Julio Huerta-Espino; Zai-feng Li; Da-qun Liu (Euphytica, 2015)

PPARα Agonist Fenofibrate Ameliorates Learning and Memory Deficits in Rats Following Global Cerebral Ischemia - Ai-Guo Xuan; Yan Chen; Da-Hong Long; Meng Zhang; Wei-Dong Ji; Wen-Juan Zhang; Ji-Hong Liu; Le-Peng Hong; Xiao-Song He; Wen-Liang Chen (Molecular Neurobiology, 2015)

Identification of genes involved in biosynthesis of mannan polysaccharides in Dendrobium officinale by RNA-seq analysis - Chunmei He; Jianxia Zhang; Xuncheng Liu; Songjun Zeng; Kunlin Wu; Zhenming Yu; Xiaojuan Wang; Jaime A. Teixeira da Silva; Zijian Lin; Jun Duan (Plant Molecular Biology, 2015)

Nondestructive Spectroscopic and Imaging Techniques for Quality Evaluation and Assessment of Fish and Fish Products - Hong-Ju He; Di Wu; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2015)

The prevalence of heifer mastitis and its associated risk factors in Huanggang, Central China - Feng Li Yang; Chen Shen; Bao Xiang He; Yu Ying Yang; Da Chun Gong; Xiao Shan Li (Tropical Animal Health and Production, 2015)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Analytical Theory for One-Dimensional Consolidation of Soil Induced by Time-Dependent Pumping and Loading - Kang-He Xie; Da-Zhong Huang; Yu-Lin Wang; Yue-Bao Deng (Marine Georesources & Geotechnology, 2014)

Migration of Ti from nano-TiO 2 -polyethylene composite packaging into food simulants - Qin-Bao Lin; He Li; Huai-Ning Zhong; Quan Zhao; Da-Hui Xiao; Zhi-Wei Wang (Food Additives & Contaminants: Part A, 2014)

An improved method to extract DNA from mango Mangifera indica - Mohammad S. Uddin; Wenli Sun; Xinhua He; Jaime A. Teixeira da Silva; Qi Cheng (Biologia, 2014)

Sorption of ammonium and phosphate from aqueous solution by biochar derived from phytoremediation plants - Zheng Zeng; Song-da Zhang; Ting-qiang Li; Feng-liang Zhao; Zhen-li He; He-ping Zhao; Xiao-e Yang; Hai-long Wang; Jing Zhao; Muhammad Tariq Rafiq (Journal of Zhejiang University-SCIENCE B, 2013)

Glycosylation analysis of recombinant neutral protease I from Aspergillus oryzae expressed in Pichia pastoris - Da Lei; Yang Xu; Qinghua He; Yifeng Pan; Bo Chen; Liang Xiong; Yanping Li (Biotechnology Letters, 2013)

Effects of position within wheat field and adjacent habitats on the density and diversity of cereal aphids and their natural enemies - Zi-Hua Zhao; Cang Hui; Da-Han He; Feng Ge (BioControl, 2013)

Effects of rainfall and manure application on phosphorus leaching in field lysimeters during fallow season - Qiao Yun Xue; Pei Bin Dai; Da Sheng Sun; Cheng Liang Sun; Ling Yu Qi; Anne Ostermann; Yao He; Xian Yong Lin (Journal of Soils and Sediments, 2013)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

Defence responses of pepper (Capsicum annuum L.) infected with incompatible and compatible strains of Phytophthora capsici - Jun-E Wang; Da-Wei Li; Ying-Li Zhang; Qian Zhao; Yu-Mei He; Zhen-Hui Gong (European Journal of Plant Pathology, 2013)

Retinoic Acid and Human Olfactory Ensheathing Cells Cooperate to Promote Neural Induction From Human Bone Marrow Stromal Stem Cells - Song-Tao Xie; Fan Lu; Xi-Jing Zhang; Qi Shen; Zuping He; Wei-Qiang Gao; Da-Hai Hu; Hao Yang (NeuroMolecular Medicine, 2013)

The association between a single nucleotide polymorphism rs11966200 in MHC region and clinical features of generalized vitiligo in Chinese Han population - Jin Tang; Jian Lan Liu; Cheng Zhang; Da Yan Hu; Su Min He; Xian Bo Zuo; Pei Guang Wang; Liang Dan Sun; Xue Jun Zhang; Sen Yang (Molecular Biology Reports, 2013)

Oxidative decarboxylation of mandelic acid derivative by recombinant Escherichia coli: a novel method of ethyl vanillin synthesis - Xiao-xia Pan; Jing-jing Li; Mei-gui Wang; Wen-sen He; Cheng-sheng Jia; Xiao-ming Zhang; Biao Feng; Da-li Li; Zeng Zeng (Biotechnology Letters, 2013)

Polymorphisms of the Interleukin 6 gene contribute to cervical cancer susceptibility in Eastern Chinese women - Ting-Yan Shi; Mei-Ling Zhu; Jing He; Meng-Yun Wang; Qiao-Xin Li; Xiao-Yan Zhou; Meng-Hong Sun; Zhi-Ming Shao; Ke-Da Yu; Xi Cheng; Xiaohua Wu; Qingyi Wei (Human Genetics, 2013)

ATP Regulates Sodium Channel Kinetics in Pancreatic Islet Beta Cells - Na Zou; Xiao Wu; Yan-Yan Jin; Meng-Zao He; Xin-Xin Wang; Li-Da Su; Marjan Rupnik; Zhen-Yong Wu; Li Liang; Ying Shen (The Journal of Membrane Biology, 2013)

Seismic deformation and seismic resistance analysis of Shapai Roller Compacted Concrete Arch Dam based on field monitoring and dynamic finite element method - Li Zhuo; Jiang-da He; Hong-qiang Xie (Journal of Mountain Science, 2013)

Paenibacillus thermophilus sp. nov., a novel bacterium isolated from a sediment of hot spring in Fujian province, China - Yu Zhou; Sheng Gao; Da-Qiao Wei; Ling-Ling Yang; Xing Huang; Jie He; Yun-Jiao Zhang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Quantifying and monitoring functional photosystem II and the stoichiometry of the two photosystems in leaf segments: approaches and approximations - Wah Soon Chow; Da-Yong Fan; Riichi Oguchi; Husen Jia; Pasquale Losciale; Youn-Il Park; Jie He; Gunnar Öquist; Yun-Gang Shen; Jan M. Anderson (Photosynthesis Research, 2012)

Association between the XRCC3 polymorphisms and breast cancer risk: meta-analysis based on case–control studies - Xiao-Feng He; Wu Wei; Jiao Su; Zi-Xuan Yang; Yi Liu; Ying Zhang; Da-Peng Ding; Wei Wang (Molecular Biology Reports, 2012)

Secretory expression and characterization of a soluble laccase from the Ganoderma lucidum strain 7071-9 in Pichia pastoris - Jing Sun; Ri-He Peng; Ai-Sheng Xiong; Yongsheng Tian; Wei Zhao; Hu Xu; Da-Tong Liu; Jian-Min Chen; Quan-Hong Yao (Molecular Biology Reports, 2012)

XPD Lys751Gln polymorphism and esophageal cancer susceptibility: a meta-analysis of case–control studies - Da-Peng Ding; Wen-Li Ma; Xiao-Feng He; Ying Zhang (Molecular Biology Reports, 2012)

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

Methylated promoters of genes encoding protocadherins as a new cancer biomarker family - Xinbing Sui; Da Wang; Shumin Geng; Gongli Zhou; Chao He; Xiaotong Hu (Molecular Biology Reports, 2012)

The cyclophosphamide metabolite, acrolein, induces cytoskeletal changes and oxidative stress in Sertoli cells - Feng Liu; Xu-Liang Li; Tao Lin; Da-Wei He; Guang-Hui Wei; Jun-Hong Liu; Lu-Sheng Li (Molecular Biology Reports, 2012)

Clostridium beijerinckii mutant obtained by atmospheric pressure glow discharge producing high proportions of butanol and solvent yields - Ting Guo; Yan Tang; Yong-lan Xi; Ai-yong He; Bai-jun Sun; Hao Wu; Da-feng Liang; Min Jiang; Ping-kai Ouyang (Biotechnology Letters, 2011)

Sub-chronic effect of perfluorooctanesulfonate (PFOS) on the balance of type 1 and type 2 cytokine in adult C57BL6 mice - Guang-Hui Dong; Miao-Miao Liu; Da Wang; Li Zheng; Zai-Fu Liang; Yi-He Jin (Archives of Toxicology, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Polymorphisms in the calcineurin genes are associated with the training responsiveness of cardiac phenotypes in Chinese young adults - Zi-Hong He; Yang Hu; Yan-Chun Li; Da-Peng Bao; Jonatan R. Ruiz; Alejandro Lucia (European Journal of Applied Physiology, 2010)

Laboratory study of fluid viscosity induced ultrasonic velocity dispersion in reservoir sandstones - Tao He; Chang-Chun Zou; Fa-Gen Pei; Ke-Ying Ren; Fan-Da Kong; Ge Shi (Applied Geophysics, 2010)

UNC-64 and RIC-4, the plasma membrane-associated SNAREs syntaxin and SNAP-25, regulate fat storage in nematode Caenorhabditis elegans - Qiu-Li Wu; Qi Rui; Ke-Wen He; Lu-Lu Shen; Da-Yong Wang (Neuroscience Bulletin, 2010)

Trigonostemon tuberculatus (Euphorbiaceae), a peculiar new species from Yunnan Province, China - Du Fan; He Ju; Yang Shao-Yong; Cheng Xia; Zhang Da-Cai; Tang Ye-Na (Kew Bulletin, 2010)

Retinoid X receptor agonists inhibit phorbol-12-myristate-13-acetate (PMA)-induced differentiation of monocytic THP-1 cells into macrophages - Lei Zhou; Ling-hong Shen; Liu-hua Hu; Heng Ge; Jun Pu; Da-jun Chai; Qin Shao; Li Wang; Jin-zhang Zeng; Ben He (Molecular and Cellular Biochemistry, 2010)

Regulation of aging by unc-13 and sbt-1 in Caenorhabditis elegans is temperature-dependent - Ke-Wen He; Lu-Lu Shen; Wen-Wen Zhou; Da-Yong Wang (Neuroscience Bulletin, 2009)

Low Genetic Variability of Domestic Muscovy Duck (Cairina moschata) in China Revealed by Mitochondrial DNA Control Region Sequences - Shi-Yi Chen; Da-Qian He; Yi-Ping Liu (Biochemical Genetics, 2009)

Demographic trade‐offs in a neutral model explain death‐rate–abundance‐rank relationship - Kui Lin; Da-Yong Zhang; Fangliang He (Ecology, 2009)
The neutral theory of biodiversity has been criticized for its neglect of species differences. Yet it is much less heeded that S. P. Hubbell's definition of neutrality allows species to differ in their birth and death rates as long as they have an equal per capita fitness. Using the lottery model of competition we find that fitness equalization through birth–death trade‐offs can make species coexist longer than expected for demographically identical species, whereas the probability of monodominance for a species under zero‐sum neutral dynamics is equal to its initial relative abundance. Furthermore, if newly arising species in a community survive preferentially they are more likely to slip through the quagmire of rareness, thus creating a strong selective bias favoring their community membership. On the other hand, high‐mortality species, once having gained a footing in the community, are more likely to become abundant due to their compensatory high birth rates. This unexpected result explains why a positive association between species abundance and per capita death rate can be seen in tropical‐forest communities. An explicit incorporation of interspecific trade‐offs between birth and death into the neutral theory increases the theory's realism as well as its predictive power.

Mapping QTLs of traits contributing to yield and analysis of genetic effects in tetraploid cotton - Dao-Hua He; Zhong-Xu Lin; Xian-Long Zhang; Yi-Chun Nie; Xiao-Ping Guo; Chun-Da Feng; James McD. Stewart (Euphytica, 2005)

Simultaneous removal of nitrate and heavy metals by iron metal - Zhi-wei Hao; Xin-hua Xu; Jian Jin; Ping He; Yong Liu; Da-hui Wang (Journal of Zhejiang University-SCIENCE B, 2005)

Isolation and characterization of rice mutants compromised in Xa21-mediated resistance to X. oryzae pv. oryzae - G. L. Wang; C. Wu; L. Zeng; C. He; M. Baraoidan; F. de Assis Goes da Silva; C. E. Williams; P. C. Ronald; H. Leung (Theoretical and Applied Genetics, 2004)

Gold Immunolocalization of Rubisco and Rubisco Activase in Pyrenoid of Chlamydomonas reinhardtii - Pei-Min He; Da-Bing Zhang; Geng-Yun Chen; Qi-Gen Liu; Wei-Ning Wu (Algae, 2003)

Differential expression of the Quox-1 gene in normal human cells, early human embryo, and tumor cells - Fan Zhu; Wen-Xin Li; Da-He Jiang; De-Ming Gou (Cell and Tissue Research, 2002)

Equitable utilisation and effective protection of sharing transboundary water resources: international rivers of western China - He Da-ming; Liu Xiu-juan (Journal of Geographical Sciences, 2001)

Fresh snow chemistry from high mountain regions in central himalayas - Shi-chang Kang; Da-he Qin; Tan-dong Yao; A. Mayewski Paul; Whitlow Sallie (Chinese Geographical Science, 2000)

Ri-mediated transformation of Artemisia annua with a recombinant farnesyl diphosphate synthase gene for artemisinin production - Da-Hua Chen; Chang-Jun Liu; He-Chun Ye; Guo-Feng Li; Ben-Ye Liu; Yu-Ling Meng; Xiao-Ya Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)